Multiphysics modelling of MICP grouting for drawdown control and curtain stability in confined aquifers with partially penetrating barriers during deep excavation - Sharif Nyanzi Alidekyi; Jianxiu Wang; Weiqiang Pan; Muhammad Arslan Ahmad; Yanxia Long; Naveed Sarwar Abbasi; Aamir Khan Mastoi (Computers and Geotechnics, 2027)

Multifunctional synergistic biomass-based composites: integrated design for energy conversion, electromagnetic shielding, and microwave absorption - Yinao Jiao; Shengjie Sui; Yifei Long; Guozhi Fan; Haitao Yang; Cheng Pan (Bioresource Technology, 2027)

An elastic-plastic constitutive model considering bonding breakage and composition for gas hydrate-bearing sediments - Pan Wang; Jian-bing Chen; Bin Zhi; En-long Liu; Xiao-chan Wang (European Journal of Environmental and Civil Engineering, 2026)

Reverse genetics platform for tomato mottle mosaic virus: infectious clone construction and resistance screening in tomato - Thuy T. B. Vo; Marjia Tabassum; Bupi Nattanong; Hyo-Jin Im; Minkwan Kim; Li-Long Pan; Hee-Seong Byun; Hae-Ryun Kwak; Sukchan Lee (Molecular Biology Reports, 2026)

Rice panicle detection from unmanned aerial vehicle (UAV) imagery via image restoration and pseudo-depth prior - Pan Pan; Haochun Li; MingXia Li; Saiyang Xu; Zhihao Guo; Guoping Yu; Long Yi; Maomao Li; Guomin Zhou; Jianhua Zhang (Computers and Electronics in Agriculture, 2026)

Multiscale investigation of lithium and gallium occurrence in coal gangue via combined in situ characterization and density functional theory calculations - Lei Zhang; Yijie Gao; Jinhe Pan; Cheng Liu; Xin He; Xin Long; Mengmeng Shi; Yu Chen; Changchun Zhou; Jinpeng Feng (Minerals Engineering, 2026)

Performing comprehensive nutrient recovery through the integration of selective electrodialysis with reverse osmosis by using synthetic swine wastewater - Jingwei Xu; Yahui Huang; Zhi-Long Ye; Xiaofang Pan; Yenan Li; Lifeng Lin (Desalination, 2026)

A climatic threshold regulating Cenozoic silicate weathering and climate stability - Pan Zhang; Kang-Jun Huang; Yan Hu; Fang-Zhen Teng; Long Ma; Tian-Yi Huang (Earth and Planetary Science Letters, 2026)

Hydroclimatic dynamics over the western Tibetan Plateau since the Last Glacial Maximum: A critical review - Kashif Hayat; Jianghu Lan; Peng Cheng; Haoran Li; Xingxing Liu; Jiansen Li; Xiaohui Wu; Long Pan; Dexiang Gan; Hong Yan; Youbin Sun (Earth-Science Reviews, 2026)

A novel model (SED-GNDE) integrating graph neural differential equations with selective electrodialysis process for nutrient prediction from synthetic wastewater - Yahui Huang; Zhi-Long Ye; Xiaofang Pan; Jianzhi Huang; Lifeng Lin (Water Research, 2026)

Sub-critical dynamic ventilation for tunnel fire safety: A physical model-driven adaptable control method - Junfeng Chen; Dong Yang; Zeng Long; Rongliang Pan (Tunnelling and Underground Space Technology, 2026)

Study on the size effect model of mode I fracture characteristics in Longmaxi formation shale based on DIC and acoustic emission technology - Yu Suo; Xian-hang Wei; Gui-quan Wang; Cui-long Kong; Guang-chao Zhang; Xi Chen; Xiaofei Fu; Zhe-jun Pan; Bin Huang (Soil Dynamics and Earthquake Engineering, 2026)

Domain-knowledge-guided deep learning for probabilistic precipitation downscaling over southeastern Tibetan Plateau - Dayang Li; Baoxiang Pan; Yuan Liu; Ashish Sharma; Yan Zhou; Yi Yao; Jun Yin; Long Yang (Journal of Hydrology, 2026)

Ferrihydrite sulfidation transformation reduces the mobilization of coexisting cadmium under anoxic conditions: Insights into the transformation mechanism - Xiaoming Zhao; Yifei Wang; Yu Song; Xu Ma; Ning Chen; Leo Ka Long Cheung; Ayetullah Tunc; Reza Deevsalar; Jinru Lin; Yuanming Pan; Haibo Li (Hydrometallurgy, 2026)

Hydrogeochemistry, source apportionment, and Monte Carlo-based health risks of heavy metals in a Carlin-type gold mining area of karst region, Southwest China - Qiguo Hu; Pan Wu; Xuefang Zha; Ke Wang; Ruixue Zhang; Bo Li; En Long (Environmental Pollution, 2026)

Printable environmentally robust hydrophobic eutectogel sensors with high strength and strong adhesion for human–machine interaction - Qianyu Wei; Weicheng Gao; Tianze Zhang; Lixia Long; Jin Zhao; Lizhi Pan; Xubo Yuan (Chemical Engineering Journal, 2026)

Prediction of available energy in Baijiu distillers’ dried grains for growing pigs based on chemical composition and computer-controlled simulated digestion approaches - Xin Guo; Kaifeng Lian; Yahui Chen; Jiajun Ye; Mengting Wang; Jiaqi Zhang; Weiyun Zhu; Long Pan; Kaifan Yu (Animal Feed Science and Technology, 2026)

EXtreme Gradient Boosting for Lithology Identification with Well Logs: A Case Study from the Salt Lake Area, Eastern Qaidam Basin, China - Zhong-yi Duan; Fu-long Zheng; Hang-yu Yue; Jia-pan Yan; Kun Xiao; Ting-yan Zhang; Jia-dong Yan (Applied Geophysics, 2026)

Synergistic effects of trehalose and cycloastragenol on long-term cryopreservation of porcine ear-margin tissue - Qi Zhou; Yu Pan; Liang Zhang; Qingpeng Yu; Lijuan Zhang; Zhi Tu; Hongmei Pan; Xi Long (Theriogenology, 2026)

Site-specific associations between soil methylmercury accumulation and plant, soil, and hgcA-associated microbial modules across Chinese coastal wetlands - Yuechen Tan; Weiwei Liu; Xu Pan; Songyuan Long; Yukun Hu; Lijuan Cui; Manyin Zhang (Journal of Hazardous Materials, 2026)

Revealing the dynamic cooling characteristics of thermoelectric cooler under periodic current input - Ding Luo; Hengliang Zhang; Long Cheng; Jiangru Pan; Kaifeng Wang; Peng Zhang; Hao Chen (International Journal of Refrigeration, 2026)

Fermentation modulates wheat germ gliadin-based nanodelivery systems loaded with wheat bran polyphenols: Physicochemical properties, interaction mechanism, and functional performances - Ai-Mei Liao; Shao-Kang Yang; Meng-Yu Gao; Siyi Han; Long Pan; Jayani Chandrapala; Haiyan Gao; Dandan Zhai; Jun-Wei Chen; Na Liu; Peng Li (Food Bioscience, 2026)

Tuning interfacial sulfur vacancy level of ZnIn2S4 for boosting photocatalytic water purification - Peng-Peng Duan; Yong-Sheng Tan; Heng-Heng Guo; Zhi-Cheng Pan; Ya-Meng Dong; Yun-long Wei; Qi-Nian Wang; Xing Zhang (Environmental Research, 2026)

Synergistic design of UV-shielding interfacial layers and hybrid filler networks for mechanically robust and UV-resistant natural rubber latex films - Long Zheng; Xiaoda Pan; Shuya Miao; Hongtao Liu; Xiaohong Liu; Xianze Yin; Chongzhi Sun; Shipeng Wen (Chemical Engineering Journal, 2026)

Can river chemistry in a karst region under human influences be used for catchment rock weathering estimation? - Yan Liu; Y. Jun Xu; Xingxing Cao; Guangxi Long; Pan Wu; Zhangxing Liu (Applied Geochemistry, 2026)

Wheat germ protein in functional foods: structure, processing, applications, and mechanistic insights - Long Pan; Jing-Yang Cai; Ai-Mei Liao; Lin-Lin Ding; Yin-Chen Hou; Ji-Hong Huang; Xin Wang; Ya-Wei Zhao; Na Liu; Zhao-Jun Wei (Critical Reviews in Food Science and Nutrition, 2026)

Differential fouling behaviors of standard and monovalent-selective membranes by digestate-derived dissolved organic matter in selectrodialysis - Xiaofang Pan; Jingwei Xu; Yenan Li; Yahui Huang; Victor Nikonenko; Natalia Pismenskaya; Zhi-Long Ye (Water Research, 2026)

Resource-oriented volatile fatty acid production and in situ recovery from food wastewater via integrated biocarrier-membrane anaerobic fermentation - Bizhen Zeng; Yuechao Wang; Kai Chen; Tianyu Li; Zhenxiang Pan; Long Chen; Lan Yang; Hongtao Zhu (Resources, Conservation and Recycling, 2026)

Active flow control of energy harvester via deep reinforcement learning to enhance energy harvesting with different Reynolds number - Fengbo Long; Xingxia Wu; Rongjie Pan; Lei Yan; Gang Hu; Jie Song (Ocean Engineering, 2026)

Influences of hydrology and anthropogenic activities on source and quality of dissolved organic matter in karst headwater streams - Shiqin Chen; Y.Jun Xu; Pan Wu; Xingxing Cao; Guangxi Long; Zhangxing Liu (Journal of Hydrology, 2026)

Design and optimization of an autothermal solid oxide electrolysis cell reactor for efficient and economical solar-driven carbon dioxide reduction - Zihan Lin; Junjie Hou; Haoran Li; Qi Xia; Jiale Long; Zhouxin Pan; Muhammad Sajid Khan; Chen Chen (Journal of Cleaner Production, 2026)

Influences of land use change on dissolved carbon in karst headwater streams - Guangxi Long; Xingxing Cao; Y. Jun Xu; Pan Wu; Shouyang He; Zhangxing Liu (Journal of Environmental Sciences, 2026)

Recombinant bovine αs1-casein as an enhanced precursor for sleep-promoting peptides: A structural, peptidomic, and molecular docking study - Long Pan; Lin-Lin Ding; Meng-Jia Song; Xiang-Li Mu; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Guang-Hai Yu (Food Bioscience, 2026)

Flexural performance of precast segmental concrete beams with externally prestressed hybrid steel-GFRP tendons - Long Pan; Zhuo Zeng; Rongxiong Gao; Zhenyu Wang (Engineering Structures, 2026)

Effects of depositional heterogeneity on cover-collapse sinkholes resulting from engineering dewatering in the Pearl River Delta (China): Risk assessment and early warning methodology - Long Jia; Yan Meng; Lujuan Li; Xiaolong Shi; Zongyuan Pan; Fubiao Zhou; Renchao Yin (Engineering Geology, 2026)

Lycii Fructus-derived extracellular vesicles-like particles attenuate sodium iodate-induced retinal injury by transporting bioactive cargo molecules - Pan Huang; Xiao-Bo Zhang; Jia-Qi Li; Guan-Wen He; Ying Chen; Ling-Yun Yang; Zai-Long Chi (Chemical Engineering Journal, 2026)

Magnetic droplet carrier robot integrated with AI-fueled on-site detection - Long Jiao; Wentao Yan; Yanjun Hu; Dongliang Li; Zhenting Xie; Zibing Pan; Qianqian Guo; Xiao Yan; Xiang Wu; Qi Wu (Chemical Engineering Journal, 2026)

Spatiotemporal variations in water quality and geochemical processes in an acid mine drainage-affected Karst river: Insights from multivariate water quality indices and statistical analyses - Changmei Yao; Yeye Ren; Pan Wu; Guangxi Long; Xingxing Cao (Acta Geochimica, 2026)

Assessment of the Immunological Effects of DNA Vaccines Carrying Antigen Genes for OVA , OMP and OVA ‐ OMP Against Aeromonas hydrophila and Aeromonas caviae Infections in Sinocyclocheilus grahami and Oreochromis niloticus - Long Zhu; Guowen Zhang; Haitao Gao; Jun Chen; Shouyou Bai; Weibin Li; Zhiqiang Feng; Jinrong Li; Lincong Yuan; Xiaofu Pan; Wenhui Li (Journal of Fish Diseases, 2026)
Aeromonas hydrophila and Aeromonas caviae are two economically significant pathogenic bacteria in aquaculture and are the main causes of bacterial septicemia in fish. Controlling disease caused by these two bacterial pathogens is becoming a greater challenge due to increases in the antibiotic resistance of bacteria. Here, we developed and applied novel DNA vaccines carrying antigen genes for ovalbumin (OVA) and the outer membrane protein (OMP) of A. hydrophila to evaluate their immunoprotective effects against these two Aeromonas species and promote the green development of the aquaculture industry. Sinocyclocheilus grahami ( S. grahami ) and Oreochromis niloticus ( O. niloticus ) were subjected to oral vaccination treatment for a total of 21 days. Seven days after being injected with 100 μL of 1 × 10 9 CFU/mL of A. hydrophila or A. caviae , significant decreases were observed in the following non‐specific immune indicators: superoxide dismutase (SOD), complement C3 (C3), lysozyme (LZM) and immunoglobulin M (IgM). However, levels of SOD, C3, LZM and IgM remained stable in fish serum following administration of the OVA, OMP and OVA‐OMP vaccines. Histopathological analysis indicated that oral vaccination with the OVA vaccine could alleviate the splenic lesions caused by A. hydrophila and A. caviae in S. grahami . After challenge with A. hydrophila , the immune protection rates of the OVA, OMP and OVA‐OMP vaccines in S. grahami were 92.56%, 88.89% and 73.33%, respectively, and the relative percent survival (RPS) of O. niloticus was 75%, 83.38% and 50%, respectively. Following challenge with A. caviae , the RPS values for S. grahami vaccinated with the OVA, OMP and OVA‐OMP vaccines were 100%, 86.96% and 95.70%, respectively, and the RPS values for O. niloticus were 92.27%, 96.19% and 92.27%, respectively. In conclusion, oral administration of the OVA, OMP and OVA‐OMP DNA vaccines significantly enhanced both non‐specific and specific immune responses, providing strong protection against A. hydrophila and A. caviae infections in S. grahami and O. niloticus . Future work should focus on optimizing vaccine stability (e.g., improving the OVA‐OMP fusion construct), expanding coverage to other economically important and endangered fish species and clarifying long‐term immune memory mechanisms to support sustainable aquaculture development.

Hydrochemical and isotopic tracers reveal mining-induced changes in river water quality and carbon flux in the karst catchment of Daiyang river - Yeye Ren; Xingxing Cao; Pan Wu; Quanzhou Gao; Changmei Yao; Guangxi Long; Weihua Tang; Deshuai Zhang; Haicheng Zhang (Journal of Hydrology, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

The influence of layered roof on the stability of lunar lava tubes - Xufeng Liu; Peng-Zhi Pan; Long Xiao; Jiannan Zhao; Zhaofeng Wang; Yi Xie; Yage Wang; Yujie Feng; Dewei Du (Icarus, 2026)

Comprehensive characterization of interrelations between pork quality, flavor and colonic microbiota in Duroc × Landrace × Yorkshire pigs - Dongfang Wang; Yiyan Liao; Jiaqiao Peng; Qiubo Wang; Long Pan; Yong Su; Weiyun Zhu (Food Research International, 2026)

Laboratory study on a new enhancing method for an in-service crushed-rock embankment underlain by permafrost - Yanbo Hao; Yuanhong Dong; Miaomiao Bai; Yanjun Ji; Jiafan Zhang; Huimei Zhang; Long Jin; Donggen Chen; Xusheng Wan; Zhongrui Yan; Jianguo Lu; Pan Chen (Cold Regions Science and Technology, 2026)

Suicide attempt risk among patients receiving methylphenidate: a retrospective cohort study - Tai-Long Pan; Li-Chi Chen; Ju-Wei Hsu; Ya-Mei Bai; Shih-Jen Tsai; Tzeng-Ji Chen; Mu-Hong Chen (Psychopharmacology, 2026)
Background Methylphenidate may reduce suicide risk among patients with attention-deficit hyperactivity disorder. Several studies have noted that the association between methylphenidate use and suicidality is weakening. Methods Data were collected from Taiwan’s National Health Insurance Research Database to assess the association between methylphenidate exposure and suicide attempt risk across two exposure periods (main analysis: 2001–2002; duplication analysis: 2004–2005). We compared suicide attempt risk between patients who initiated methylphenidate treatment and those with no recorded psychiatric treatment or methylphenidate exposure during the same period. Results In both the main and duplication analyses, patients receiving methylphenidate exhibited a higher subsequent risk of suicide attempts than unexposed individuals. A duration–response pattern was observed in both cohorts: the hazard ratio of suicide attempts declined with longer cumulative methylphenidate use, from 1.60/1.84 for < 30 days to 1.45/1.65 for ≥ 180 days. Because hazard ratios were closely aligned across 2001–2002 and 2004–2005, the association of methylphenidate with reduced suicide attempt risk did not appear to decrease over time. Discussion Longer use of methylphenidate was associated with a lower risk of subsequent suicide attempts among patients in Taiwan receiving methylphenidate. The beneficial effect of methylphenidate on suicide risk remained consistent over time.

Fungal-driven carbon sequestration within soil aggregates under paddy multicropping - Wei Zhang; Wen Liu; Leyan Zhang; Mengyao Zhou; Rui Xiong; Hongling Qin; Anlei Chen; Baoli Zhu; Zhiqiang Fu; Pan Long (Applied Soil Ecology, 2026)

Stress Interference between Multi-radial Boreholes During Hydraulic Fracturing in Multilayered Reservoirs Based on the Discrete Lattice Method - Tengda Long; Xiaoguang Wu; Yazhou Shen; Zixiao Xie; Zhongwei Huang; Gensheng Li; Rui Yang; Zhaowei Sun; Tao Pan; Naikun Hu; Xiaohua Wang (Rock Mechanics and Rock Engineering, 2026)

Coordinate fixed and mobile charging station deployment and scheduling for fluctuating demand - Chen Peng; Yang Yang; Enjian Yao; Long Pan; Yuting Zhu (Transportation Research Part D: Transport and Environment, 2026)

Ancient massive dolomites: The present is the key to the past - Pan Zhang; Kang-Jun Huang; Dong Feng; Long Ma; Weihai Xu; Wen Yan (Sedimentary Geology, 2026)

Corrigendum to “Calcium silicate hydrate from simulated alkali-activated industrial waste residue: Adsorption and immobilization mechanism of Pb2+ and Mn2+” [J. Water Process Eng. 87 (2026) 110126] - Wenzhuo Lu; Qingyuan Liu; Huiyi Huang; Junzhang Ling; Ouxu Pan; Rongmiao Gan; Wanting Liu; Xinru Yang; Tengfa Long (Journal of Water Process Engineering, 2026)

A comparison of in-situ and ex-situ phosphonate HEDP removal from industrial reverse osmosis concentrate by Fe(II)/calcium peroxide process: Implications for total phosphorus (TP) management - Jin Xia; Yi Wang; Xiaochang Huang; Xiang Li; Xuejun Long; Jun Wan; Jiaqi Ding; Fei Pan (Journal of Environmental Chemical Engineering, 2026)

Mechanistic insight into the “intermediate effect”: Competitive adsorption and surface coverage model in controlling hydrate formation in a closed-cell foam–SDS system - Yi-Feng Wang; Zhen-Guo Qi; Zhen Pan; Li-Yan Shang; Zhi-Ming Liu; Jie Liu; Zhuo-Fan Ma; Long-Qi Meng (Chemical Engineering Journal, 2026)

Analysis of wind data consistency derived from wind profile and L-band sounding radar based on ICC - Fang Pang; Yu Long Han; Yi Pan; Ming Yi Gu; Yansong Bao; George P. Petropoulos (International Journal of Remote Sensing, 2026)

Early detection of cotton Verticillium wilt using hyperspectral and chlorophyll fluorescence imaging fusion - Fei Tan; Tianying Yan; Long Duan; Wei Chen; Jingkun Yan; Ruoyu Di; Xiuwen Gao; Nianyi Wu; Xin Lv; Pan Gao (Computers and Electronics in Agriculture, 2026)

Hydraulic mechanisms of landform genesis during catastrophic outburst floods in the middle Yarlung Tsangpo River, Tibetan Plateau - Xiaolu Dong; Shuangwen Yi; Xiaolin Qin; Long Yang; Baotian Pan; Zhijun Zhao; Huayu Lu; Xianyan Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Calcium silicate hydrate from simulated alkali-activated industrial waste residue: Adsorption and immobilization mechanism of Pb2+ and Mn2+ - Wenzhuo Lu; Qingyuan Liu; Huiyi Huang; Junzhang Ling; Ouxu Pan; Rongmiao Gan; Wanting Liu; Xinru Yang; Tengfa Long (Journal of Water Process Engineering, 2026)

Effects of digital economy-driven Chinese-style agricultural modernisation--based on analysis of mediating effects and spatial spillovers - Pan Hong; Tan Shuang; Liu Mingyu; Ying Xie; Suwan (Cheng) Long (Journal of Rural Studies, 2026)

Fermented wheat germ attenuates metabolic dysregulation in offspring induced by maternal high-fat diet: insights from multi-omics analyses - Xiaolin Li; Yingyu Zhao; Aimei Liao; Long Pan; Yurong Xing; Jingjing Cheng; Jin Liu; Jihong Huang (Food Bioscience, 2026)

Metabolic and physiological mechanisms underlying enhanced ε-poly-L-lysine biosynthesis in Streptomyces albulus under ethanol stress - Yi-Hang Chen; Xiao-Yu Wu; Yu Zhou; Xin-Xin Guo; Xu-Sheng Chen; Quan-Ping Liu; Ai-Mei Liao; Yin-Chen Hou; Long Pan (Food Bioscience, 2026)

Preparation and application of ergothioneine liposomes and their inhibitory effect on polyphenol oxidase from Lanzhou lily - Wenguang Fan; Shuyuan He; Haiwei Ren; Lichao Pan; Long Liu; Yaqin Tian (Food Bioscience, 2026)

Cryoprotective effects and mechanisms of heterologously expressed wheat-derived antifreeze peptide on probiotics - Xiaoge Liu; Jingjing Wang; Yingjing Qu; Long Pan; Xin Wang; Kangyi Zhang; Quan-Ping Liu; Na Liu; Jihong Huang; Ai-Mei Liao (Food Bioscience, 2026)

Quinolones, tetracyclines, and amphenicols in animal-derived food products from southeast China: distribution and health risk estimation - Hai-Tao Shen; Jian-Long Han; Xiao-Min Xu; Xiao-Dong Pan (Food Control, 2026)

Molecular switch engineering manipulates Zn ion transfer enabling fast charging Zn-ion batteries - Yuying Li; Qing Xin; Pan Feng; Junnan Qu; Jingxuan Ren; Jiahao Lei; Jinhao Chen; Jingyao Li; Renming Liu; Xintao Long; Xinli Guo; Dan Luo; et al. (Chemical Engineering Journal, 2026)

Predicting Rate of Penetration of Horizontal Wells Based on the Di-GRU Model - Tao Pan; Xianzhi Song; Baodong Ma; Zhaopeng Zhu; Lin Zhu; Muchen Liu; Chengkai Zhang; Tengda Long (Rock Mechanics and Rock Engineering, 2026)

Assessing NEX-GDDP-CMIP6 for extreme-temperature simulation in Northwest China and projecting changes under SSP-based scenarios - Qian Li; Tongfei Zhang; Shuang Wang; Xiaohua Fu; Long Cheng; Pan Wang; Juan Feng (Climate Dynamics, 2026)

Dietary red sorghum shifts colonic microbial fermentation and metabolic profiles in growing pigs - Yangguang Ren; Xinjie Liang; Yong Su; Weiyun Zhu; Long Pan (Animal Feed Science and Technology, 2026)

Realization of elastic Weyl semimetal phases with skyrmion spin textures - Yuang Pan; Liang Si; Miao Yang; Ning Han; Li Zhang; Qiaolu Chen; Rui Zhao; Fujia Chen; Yudong Ren; Wenhao Li; Yuze Hu; Mingyu Tong; et al. (Science Bulletin, 2026)

Life cycle assessment and multi-objective optimization of CO₂ capture via organic amine-based chemical absorption - Hongjuan Zhang; Yangyang Cao; Yunbing Ma; Yibo Pan; Jingying Li; Long Xu; Xiaoxun Ma (Journal of Environmental Chemical Engineering, 2026)

Unraveling the synergy of wheat-based probiotic- fermented modified dietary Fibers, resistant starch, and gluten in constructing high-quality, low Glycemic index noodles - Ai-Mei Liao; Xiao-ge Liu; Qiao-Qiao Lai; Jia-qi Wang; Kiran Thakur; Long Pan; Yin-Chen Hou; Na Liu; Xian-ming Liu; Zhao-Jun Wei (Food Chemistry, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

The effect of bile salts stress on the biology and transcriptome characteristics of Vibrio parahaemolyticus under low salt environment - Zhiyong Song; Ran Zhang; Shiying Ji; Zhengchuan Long; Yingjie Pan; Qingchao Xie; Yong Zhao; Haiquan Liu (Archives of Microbiology, 2026)

Recycling high-level liquid waste into covalent organic framework confined unsymmetrical single Pd-N2 site toward H2O2 photosynthesis - Zhi Gao; Ruitao You; Kecheng Pan; Qingsheng Huang; Zhenzhen Xu; Long-Shuai Zhang; Jian-Ping Zou (Resources, Conservation and Recycling, 2026)

Upcycling anaerobic digestion methane to single-cell protein as a low-carbon strategy - Pan-Long Lv; Qing-Rui Hu; Yu-Yang Hu; Wenjing Gong; Qian Li; Rong Chen (Resources, Conservation and Recycling, 2026)

Lipid metabolic dysregulation: A novel developmental toxicity pathway of aged nanoplastics via inhibition of lipophagy in zebrafish - Wanjing Liu; Sihong Long; Xiaojie Wen; Mingjie Yang; Haoran Hu; Yufan Pan; Chunhua Zhan; Fei Yang (Journal of Hazardous Materials, 2026)

Wolframite and cassiterite geochemistry deciphers W–Sn ore formation: A case study from the Zuoba quartz-vein tungsten deposit, South China - Kai-Han Zhang; Jun-Yi Pan; Pei Ni; Gen-Wen He; Lin-Lin Peng; Ming-Sen Fan; Yuan-Long Zhang; Wen-Sheng Li (Journal of Asian Earth Sciences, 2026)

Frequency-magnitude analysis of megafloods: Quantifying sediment transport and geomorphic effectiveness in the Tsangpo Gorge, eastern Himalaya - Xiaolu Dong; Xianyan Wang; Elad Dente; Long Yang; Baotian Pan; Huayu Lu (Geomorphology, 2026)

Recombinant bovine lactoferrin ameliorates cold stress-induced immunosuppression by modulating the gut microbiota in mice - Lin-Lin Ding; Haiyan Sun; Xuan-Yi Xu; Yu Zhang; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Long Pan (Food Bioscience, 2026)

Solidification of high water content marine deposits by a novel in-situ treatment of magnesia-based bio-cement: Insight from clay content effect - Dian-Long Wang; Wen-Bo Chen; Hao-Yu Fang; Zhen-Yu Yin; Xiao-Hua Pan; Chao-Sheng Tang (Engineering Geology, 2026)

Ecological effects and strategies of Spartina alterniflora Loisel. removal in China - Zhanbin Luo; Fu Chen; Xi-En Long; Jing Ma; Jiyou Wei; Yudi Guo; Yanfeng Zhu; Yongjun Yang; Xiaoping Ge; Yanyan Kang; Ming Zou; Lei Liu; et al. (Environmental Impact Assessment Review, 2026)

Monodisperse lutetium-177-labeled poly(lactic acid) microspheres for radioembolization therapy of hepatocellular carcinoma - Qing-Rong Jiang; Ping He; Ling-Yun Guo; Qi-Yi Mo; Xing-Long Zhou; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Wen-Jie Zhang; Xiao-Jie Ju; Liang-Yin Chu (Chemical Engineering Journal, 2026)

Optimal glycine betaine threshold for enhancing partial denitrification-anammox performance under carbon starvation: Mechanisms and microbial responses - Jing Chen; Xinyu Long; Lei Zhu; Jianhui Wang; Menglu Pan; Yiyi Deng; Lisha Guo; Zhenguo Chen; Hong Chen (Bioresource Technology, 2026)

Decoding microglial metabolic cell death and PANoptosis hub genes in subacute phase of traumatic brain injury: a multi-omics and experimental validation study - Zhe Wu; Bao-ya Yang; Jin-qing Lai; Shi-hong Lin; Long Lin; Jian-long Chen; Jia-xiang Pan; Yao-xin Ruan; Xiang-rong Chen (Apoptosis, 2026)

A novel phage and its protective effects against Hafnia paralvei in Cyprinus carpio Koi - Lingting Pan; Chenxin Qu; Wencai Liu; Long Tan; Xiaoying Jing; Jinpeng Xu; Wei Lin; Dengfeng Li; Yigang Tong (Aquaculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Evolution of the westerlies and the East Asian winter monsoon during the late Miocene and Pliocene - Yan Zhao; Long Ma; Kang-Jun Huang; Yuanqiang Guo; Feng Pan; Ruiming Chen; Jianxing Li; Qi Wang; Jianan Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Understanding travel behavior change with megacity development: Insights from decade-long household travel surveys in Beijing - He Hao; Enjian Yao; Long Pan; Yang Yang; Yue Wang (Journal of Transport Geography, 2026)

Human activities and horizontal gene transfer shape the resistome landscapes of non-human primates - Yue Sun; Mingyi Zhang; Yang Teng; Yueqi Yin; Jingcheng Ran; Haijun Su; Hongjia Li; Xiaolong Huang; Zexu Long; Xue Sun; Huijuan Pan; Xiaochen Wang; et al. (Journal of Hazardous Materials, 2026)

Mechanistic insights into natural chalcopyrite catalyzed photo-Fenton degradation of chlortetracycline: Synergistic activation pathways and environmental implications - Xinyu Chen; Jinxiang Dai; Yanyu Song; Mingtao Liu; Long D. Nghiem; Fei Pan; Xianbo Sun; Zhengqing Cai (Journal of Environmental Chemical Engineering, 2026)

Discovery of ActRIIB antagonistic peptides from in vitro-digested chicken breast meat via an integrated Peptidomics and molecular docking approach - Fei Zhao; Junwei Yan; Zhiguo Liu; Daodong Pan; Yanli Wang; Long Li; Shikun Suo; Kuo Dang; Dongbing Li; Yali Dang; Xinching Gao (Food Research International, 2026)

Split-flow electroextraction with in-situ matrix cleanup for analysis of shellfish toxins - Hongkai Zhang; Jing Wang; Xianfeng Huang; Rongfei Peng; Juan Du; Han Xu; Chaoyang Long; Jialiang Pan (Food Chemistry, 2026)

The multi-carboxyl metal-organic framework MIL-101(Fe) effectively adsorbs total purines from whole soybean seeds - Deshuai Shao; Cui He; Na Li; Yuqing Gao; Xiaoyu Hu; Yingrun Cai; Qinqin Zhang; Jiahui Yao; Shuo Wang; Yifan Yang; Jiayi Pan; Huihui Gao; et al. (Food Chemistry, 2026)

Associations of paraben exposures measured by repeated urinary biomarkers with sperm DNA damage and apoptosis - Xiu-Ting Li; Yu Miao; Min Zhang; Jia-Yue Zeng; Peng-Hui Liu; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Ning Zhang; Long Ge; Han-Qin Ye; Pan-Pan Chen; et al. (Environmental Research, 2026)

Stage- and genotype-specific adaptation of alfalfa to calcium–drought interactions: physiological basis for karst crop breeding - Jingyi Pan; Jiyuan Zhang; Chang Liu; Sisi Long; Lili Zhao (Plant and Soil, 2026)

Effects of low-temperature storage on the physiology, biochemistry, and predation ability of Eocanthecona furcellata (Wolff) (Hemiptera: Pentatomidae) - Ling-Yi Liu; Chun-Ni Pan; Meng-Shuang Yao; Wei-Zhou; Zhi-Li Li; Hao-Jun Li; Wen-Long Chen (Phytoparasitica, 2026)

Numerical predictor-corrector based planetary atmospheric entry guidance with path constraints - Xini Niu; Jiateng Long; Shengying Zhu; Chenglong Pan (Advances in Space Research, 2026)

Integrated characterization and risk assessment of toxic elements and organic pollutants in bivalve mollusks from Southeastern China - Cheng-Zhu Ni; Xiao-Dong Pan; Jian-Long Han; Hai-Tao Shen; Xiao-Min Xu (Marine Pollution Bulletin, 2026)

Recombinant defense protease inhibitors from Vigna unguiculata show bioactivity against non-host related pests - Jia Liu; XinYue Tang; KeQian Long; ShiQi Zhou; LiLong Pan; WenJia Yang; GuangMao Shen (Pesticide Biochemistry and Physiology, 2026)

Late Miocene climate change and orogenies jointly shaped the diversity patterns and evolution of a Neotropical cycad - Jian Liu; Shuai Long; Anders J. Lindstrom; Yi-Qing Gong; Shan-Shan Dong; Yue-Zhi Pan; Shouzhou Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Incomplete lineage sorting, hybridization and polyploidization blurred phylogenetic relationships of gentians from the Qinghai-Tibetan Plateau - Shan-Shan Sun; Shu-Han Xu; Wen-Jie Yi; Shi-Long Chen; Pan Li; Daiki Takahashi; Harue Abe; Xiao-Lei Ma; Peng-Cheng Fu (Molecular Phylogenetics and Evolution, 2026)

Nonagricultural emissions and N2O5 hydrolysis drive wintertime inorganic nitrogen aerosol formation in Sichuan Basin: Nitrate and ammonium isotopic evidence - Xiaojuan Huang; Yuhan Long; Yuepeng Pan; Lin Han; Xiaoling Zhang; Junke Zhang; Runqi Zhang; Yingjun Chen; Jianmin Chen (Journal of Hazardous Materials, 2026)

Speciation of N, P, K nutrient elements and heavy metals in sewage sludge char produced from a pilot-scale thermal carbonization device and its utilization in soil amendment - Long Chen; Yibin Wang; Tianming Yin; Shilin Yu; Wen Sun; Chunli Zheng; Houzhang Tan; Jinwei Zhu; Zhicheng Pan (Journal of Cleaner Production, 2026)

Distinct magnesium isotope behaviours during basalt weathering under different weathering regimes - Qi Wang; Kang-Jun Huang; Shu-Yun Xie; Long Ma; Pan Zhang (Global and Planetary Change, 2026)

Comparison of pork quality and colon microbiota composition in Crossbred Pigs from Different Duroc × (Landrace × Yorkshire) pigs - Yiyan Liao; Dongfang Wang; Yan Fu; Yongqi He; Jianlan Wang; Jianzhuang Tan; Long Pan; Yong Su (Food Bioscience, 2026)

Dual-reaction-center engineering in Cu/CoFe2O4 spinel for pH-universal Fenton reaction toward efficient ofloxacin degradation - Yixin Peng; Luwen Qian; Xianbo Sun; Long D. Nghiem; Fei Pan; Jing Ji; Yongdi Liu; Zhengqing Cai (Chemical Engineering Journal, 2026)

A novel ambient-mesophilic two-phase anaerobic digestion system enhances methane production and process stability of food waste leachate under ammonia stress - Zunjing Lv; Tingting Zhang; Xiaofang Pan; Zhi-Long Ye; Donghua Xie; Guanjing Cai; Quan-Bao Zhao; Yanlin Li (Chemical Engineering Journal, 2026)

Effect of histone acetylation on plant resistance to salt stress - Tingyue Yang; Zesheng Liu; Xuejuan Pan; Wenying Wei; Caiting An; Long Li; Yuanhui Wang; Weibiao Liao; Chunlei Wang (Plant and Soil, 2026)

Performance of heavy metals in the intertidal zone surface sediments of the Yellow River Estuary under water-sediment regulation scheme - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Ma; Feng Min Pan; Jian Wei Xing; Chen Long Feng; De Tong Tian; Zhi Bo Wang; Rui Wang (Marine Pollution Bulletin, 2025)

Unveiling the functional contribution of Malpighian tubule specific glucose transporters to xenobiotics tolerance in Spodoptera litura - Long Jin; Zixin Zhang; Haoran Kong; Chengcheng Fan; Furong Mao; Yiou Pan; Qingli Shang (Pesticide Biochemistry and Physiology, 2025)

Fat body specific ABCG3 accounts for xenobiotic tolerance and is regulated by the homeobox transcription factor Bcd in Spodoptera litura - Lin Liang; Long Jin; Furong Mao; Chengcheng Fan; Haoran Kong; Zixin Zhang; Yiou Pan; Qingli Shang (Pesticide Biochemistry and Physiology, 2025)

Corrigendum to “Electrodialysis, a promising approach for nutrients recovery from anaerobic liquid digestate: Status, challenges and perspectives” [J. Water Process Eng. 72 (2025) 107658] - Xiaofang Pan; Yenan Li; Yahui Huang; Jingwei Xu; Chenyue Sun; Zhi-Long Ye (Journal of Water Process Engineering, 2025)

Evolution of water-soluble organic aerosol composition from clean days to haze episodes in rural area of North China Plain - Chun Chen; Long Jia; Zhiqiang Zhang; Jian Gao; Yanmei Qiu; Junling Li; Rui Gao; Ping Li; Qun Zhang; Zhijie Li; Jiaxing Sun; Nan Ma; et al. (Journal of Environmental Sciences, 2025)

Differential characteristics of meat flavor compounds, colonic microbiome and metabolome between Duroc × Landrace × Yorkshire pigs with high and low intramuscular fat of longissimus dorsi muscles - Dongfang Wang; Yangguang Ren; Yiyan Liao; Long Pan; Yong Su; Weiyun Zhu (Food Research International, 2025)

Corrigendum to “Effects of thermostable α-amylase and autoclave treatment-debranching on starch–lauric acid complex structure, digestibility, and thermal properties” [Food Chem. 480 (2025) 143821] - Yinchen Hou; Chuanyi Hui; Chenyu Li; Zhen Wang; Qihui Shi; Long Pan; Mingqian Gao; Mingyi Zhang; Jihong Huang (Food Chemistry, 2025)

Wheat germ peptides enhance hypoxia tolerance by modulating gut microbiota and reprogramming brain energy metabolism in mice - Jing-yang Cai; Ying-Ying Liu; Meng-Cheng Li; Xin-Xin Guo; Ai-Mei Liao; Yin-Chen Hou; Quan-Ping Liu; Yong-Chao Fan; Long Pan; Ji-Hong Huang (Food Bioscience, 2025)

Radial borehole fracturing in the multilayered shale oil reservoir based on a 3D discrete lattice model - Zixiao Xie; Tengda Long; Xiaoguang Wu; Zhongwei Huang; Gensheng Li; Xianzhi Song; Rui Yang; Tao Pan; Wenchao Zou; Zhaowei Sun; Yaoyao Sun; Naikun Hu; et al. (Engineering Geology, 2025)

Dual-mechanism defect engineering of multi-enzyme embedded ZIF-8 for efficient anthocyanin extraction from black rice - Mengyuan Cao; Bicong Wang; Yuchao Deng; Da-Wei Pan; Xiao-Jie Ju; Rui Xie; Zhuang Liu; Xing-Long Zhou; Mao-Jie Zhang; Wei Wang; Liang-Yin Chu (Chemical Engineering Journal, 2025)

Link between Double-Diffusive Staircases and Water Masses in the Arctic Ocean - Xue-Long Song; Sheng-Qi Zhou; Ling Qu; Yuan-Zheng Lu; Lu-Dan Pan (Thalassas: An International Journal of Marine Sciences, 2025)

Whole-genome duplications revealed by macronuclear genomes of five rare species of the model ciliates Paramecium - Jiahao Ni; Yue Hao; Berenice Jiménez-Marín; Farhan Ali; Jiao Pan; Yaohai Wang; Ziguang Deng; Jean-Francois Gout; Yu Zhang; Michael Lynch; Hongan Long (Science China Life Sciences, 2025)

A herbaceous peony WRKY transcription factor PlWRKY70 enhances tolerance to salt stress in transgenic Arabidopsis thaliana - Ling Tang; Weili Long; Yanhua Pan; Jiaxuan Ren; Weicheng Wang; Rong Huang; Fei Shen (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Sigma-1 receptor activation by PRE-084 attenuates sepsis-associated encephalopathy by targeting microglial p38 MAPK-mediated neuroinflammation and neuronal endoplasmic reticulum stress - Xin Zeng; Wen Kang; Qin Zhou; Xia Pan; Long Wang (Inflammation Research, 2025)

Mechanisms and mechanical behavior of acid-corroded sandstone under true triaxial unloading - Weipeng Pan; Yuchao Zheng; Lei Long; Jiahao Min; Liang Luo; Xiang He; Huijian Zhang; Peng Yang; Feng Lu (Bulletin of Engineering Geology and the Environment, 2025)

Primary and Secondary Calcite in Chinese Loess Distinguished by Crystallinity and Implications for Illuviation Depth and East Asian Summer Monsoon Intensity - Yan Zhao; Kang-Jun Huang; Yuanqiang Guo; Pan Zhang; Yawen Lu; Long Ma (Journal of Earth Science, 2025)

Metabolic syndrome and risk of dementia and cognitive decline: a systematic review and meta-analysis of prospective cohort studies from 6,753,197 participants - Qi Wang; Luyi Zhang; Ruiqi Xu; Kexin Meng; Lutong Pan; Xiaoyu Zhang; Long Ge; Dongshan Zhu (GeroScience, 2025)

Development and performance evaluation of an anoxic-aerobic combined treatment system packed with carbonate rocks for acid mine drainage - Qiang Li; Ruixue Zhang; Jipei Ao; Pan Wu; Xiaoting Long; Chuan Luo (Journal of Water Process Engineering, 2025)

Land use changes and urbanization enhance CO2 emissions from karst headwater streams - Xingxing Cao; Guangxi Long; Y. Jun Xu; Pan Wu; Shouyang He; Zhangxing Liu (Journal of Hydrology, 2025)

Insight into the carapace discoloration of black tiger shrimp (Penaeus monodon) during frozen storage from the perspective of protein - Chuang Pan; Jingrong Ma; Yuan Chai; Xiaoshan Long; Jianwei Cen; Chunsheng Li; Yongqiang Zhao (Food Chemistry, 2025)

Engineering of post-translational modification-independent one-step synthesized xanthine oxidase by refactoring the electron acceptor region of xanthine dehydrogenase - Chun-Yan Zhu; Yi-Long Wang; You Wen; Tian-Tian Gao; Xiao-Ni Huang; Xiao-Dong Pei; Dong-Lei Pan; Xiao-Ling Liu; Xin-Hui Xing; Zhi-Wei Yang; Cheng-Hua Wang (Food Bioscience, 2025)

Preparation of high-specificity monoclonal antibody based on rational hapten design and development of immunoassay for accurate detection of dexamethasone in milk and animal tissues - Hongfei Yang; Liangni Qin; Jiaxu Xiao; Xiaoming Pan; Shiyun Han; Linwei Zhang; Jixiang Liang; Yu Si; Hao Wen; Long Li; Xingyu Wang; Xiaojuan Zhang; et al. (Food Bioscience, 2025)

Evaluation of soil quality and system sustainability in ratoon rice paddy field under green manure application in central China - Ying Xu; Qiwen Hou; Jinbiao Xiang; Mutian Gao; Pufan Shao; Sheng Chen; Zhiqiang Fu; Pan Long; Cheng Huang (Field Crops Research, 2025)

Spin orbit charge transfer enhances intermolecular hydrogen atom transfer catalyzed polymerization for conductive elastomers syntheses - Qingze Pan; Saran Long; Jianwei Li; Pengzhong Chen; Junhui Wang; Kaifeng Wu; Jiangli Fan; Xiaojun Peng (Chemical Engineering Journal, 2025)

Localized surface plasmon enhancement strategy with synergistic dual-mechanism fluorescence quenching for developing highly sensitive lateral flow immunoassays - Mingyue Ding; Hao Wen; Long Li; Yu Si; Jixiang Liang; Shixiang Wu; Linwei Zhang; Hongfei Yang; Shiyun Han; Xiaoming Pan; Yiting Wang; Jiacan Wang; et al. (Chemical Engineering Journal, 2025)

Exploring the causal relationship between air pollution and aortic disease risk: a multivariable Mendelian randomization analysis - Yilin Pan; Zhaobin Sun; Junwen Chen; Long Feng; Tai Huang; Xiaonan He (Atmospheric Environment, 2025)

Impact of sodium intake on blood pressure, mortality and major cardiovascular events: an umbrella review of systematic reviews and meta-analyses - Qiuyu Yang; Robin W. M. Vernooij; Hongfei Zhu; Gihad Nesrallah; Chunyang Bai; Qi Wang; Ying Li; Danni Xia; Małgorzata M. Bała; Sylwia Warzecha; Mingyao Sun; Ahmad Jayedi; et al. (Critical Reviews in Food Science and Nutrition, 2025)

On the hotspot-Sun angular offset in urban thermal anisotropy - Wenfeng Zhan; Lu Jiang; Guanwen Chen; Jian Hang; Pan Dong; Shasha Wang; Long Li; Huilin Du (Remote Sensing of Environment, 2025)

Effects of blending ratios on underwater dispersion dynamics and rupture behaviours of hydrogen-doped natural gas - Qingyuan Wang; Yilin Yang; Long Ding; Dali Wu; Tao Chen; Xuhai Pan; Michael Short (Process Safety and Environmental Protection, 2025)

Genesis and role of bubble-like structures in rhodochrosite-rich orebodies of “Datangpo-type” sedimentary exhalative manganese deposits in China - Sui Zhang; Liangjun Yuan; Jianxi Long; Yu Liu; Wen Pan; Hongqian Shen (Journal of Asian Earth Sciences, 2025)

Experimental study of spray explosion characteristics and flame propagation in methanol blended water/ethanol - Xuhai Pan; Feng Xie; Long Ding; He Wang; Shucheng Guo; Zhenyu Wang (Fuel, 2025)

Prediction of suitable areas for Prunus serrulata Lindl. in the context of future climate change - Mengting He; Jiayiming Wang; Chunying Long; Zhiyi Zou; Ninghui Pan; Lihan Huang (Flora, 2025)

Seasonal bioaccumulation and biomagnification of typical organochlorine pesticides in the Pearl River Estuary, South China - Xutong Zhang; Yiye Jiang; Yanhong Zeng; Jian Guo; Ling Long; Zijian Pan; Yankuan Tian; Yanting Zhang; Xiaojun Luo; Pingan Peng; Bixian Mai (Environmental Pollution, 2025)

A critical review of membrane-based strategies for sustainable recovery of volatile fatty acids from anaerobic fermentation broths - Bizhen Zeng; Long Chen; Shixin Zhai; Kai Chen; Zhenxiang Pan; Lan Yang; Nasir Ali Khan; Kuichang Zuo; Hongtao Zhu (Chemical Engineering Journal, 2025)

Phosphate-mediated pseudo-selectivity in calcification control: Substrate-derived alkalinity outweighs kinetic modulation in anaerobic granular sludge - Hua Lian; Jie-De Luo; Qing-Liu Luo; Ji-Qi Pan; Ling Peng; Guang-Ning Liu; Long-Hui Zhan; Shuang-Fei Wang; Jian Zhang (Bioresource Technology, 2025)

Aged nanoplastics reprogram the ER stress-autophagy crosstalk: A mechanistic gateway to skeletal malformations in zebrafish - Sihong Long; Xiaojie Wen; Manni Dai; Yufan Pan; Wanjing Liu; Chunhua Zhan (Aquatic Toxicology, 2025)

PGC-1α Expands Neural Precursor Pool and Facilitates Cognitive Recovery Within AD Hippocampus Through the Regulation of Mitochondrial Dynamics - Yu-Xin Wang; Yi-Jie Wang; Wen Pan; Long-Fei Xu; Jia-Qing Wang; Hua Wang; Xin Qian; Cheng-Zhi Zou; Xu Zhu; Jia Wang (Molecular Neurobiology, 2025)

Bridging missing GNSS phase measurements through cycle slip detection for improved smartphone positioning - Jiahuan Hu; Wu Chen; Pan Li; Xiaolong Mi; Kai Zheng; Long Tang; Wanke Liu; Jingkai Yuan; Sunil Bisnath (Journal of Geodesy, 2025)

Recent updates on plant-derived anti-fatigue peptides as novel energy boosters: expansion from mechanisms of action and beyond - Ai-Mei Liao; Tingting Xu; Kiran Thakur; Yin-Chen Hou; Long Pan; Jihong Huang; Kangyi Zhang; Na Liu; Yuansen Hu; Xian-ming Liu; Zhao-Jun Wei (Trends in Food Science & Technology, 2025)

Assessing urban emergency medical services accessibility for older adults considering ambulance trafficability using a deep learning approach - Zhuo Liu; Enjia Zhang; Shuo Pan; Sichun Li; Ying Long; Frank Witlox (Sustainable Cities and Society, 2025)

Prediction of next-day 1-km canopy urban heat island by integrating a multi-block convolutional neural network with satellite- and ground-based observations - Shuang Ge; Wenfeng Zhan; Jiufeng Li; Long Li; Pan Dong; Xiang Li; Chenguang Wang; Chunli Wang; Yihan Gao (Sustainable Cities and Society, 2025)

Activation of O2 within confined ultramicropores of carbon electrocatalyst for enhanced electrochemical oxidation of water contaminants - Ming-Ming Wu; Yi-Xiao Pan; Liang-Long Xing; Lin-Feng Zhai; Min Sun (Journal of Hazardous Materials, 2025)

Distribution and health risk assessment of multiple elements in canned aquatic products from southeast China - Hai-Tao Shen; Xiao-Dong Pan; Lu-Nan Cao; Jian-Long Han (Food Control, 2025)

Redistribution of the post-reaction internal energies in DSMC using quantum-kinetic model - Chi-Ho Chou; Kuo-Long Pan (Computer Physics Communications, 2025)

Chemotactic response during acidogenic fermentation: The key for microorganisms to resist the stress of phthalic acid esters - Yi Zheng; Yanran Zhang; Xinyu Peng; Su Chang; Pan Wang; Bolin Zhu; Guoying Wang; Long D. Nghiem; M.A.H. Johir; Yuquan Wei; Ji Li; Xiaoping Wang (Chemical Engineering Journal, 2025)

Chitosan/PEO@Eu-MOF nanofiber membrane-based test strip for visual detection of tetracycline with smartphone-assisted analysis - Wei Pan; Zi-Han Zhu; Yan-Shen Zhao; Jie-Liu; Zhi-Guang Zhang; Gui-Xia Li; Tao Yu; Zhong-Zhi Han; Yun-Ze Long; Gui-Feng Yu (Chemical Engineering Journal, 2025)

Phosphoric waste acid meets iron-rich tailings: A closed-loop route to FePO4 - Hailin Long; Xianqing Xu; Siwei Li; Deqing Zhu; Jian Pan; Zhengqi Guo (Journal of Water Process Engineering, 2025)

Quantitative Reconstruction of Salinity and Precipitation Changes in Central Asia over the Past 3 200 Years Using Diatom and Pollen Records of Lacustrine Sediment in Aibi Lake of SW Junggar Basin - Long Pan; Guoqiang Li; Xiaoyan Wang; Ming Jin; Xinrong He; Luo Qin; Zhong Wang; Wenwei Zhao; Chunzhu Chen; Yuanlu Liu; Jin Yang; Lele Shu (Journal of Earth Science, 2025)

Decomposition in vacuum ultraviolet-based advanced oxidation/reduction processes and its relationship to physicochemical properties of target contaminants - Taiyo Akuto; Long Pan; Taku Matsushita; Rinako Kawashita; Yoshihiko Matsui; Nobutaka Shirasaki (Science of The Total Environment, 2025)

Effects of thermostable α-amylase and autoclave treatment-debranching on starch–lauric acid complex structure, digestibility, and thermal properties - Yinchen Hou; Chuanyin Hui; Chenyu Li; Zhen Wang; Qihui Shi; Long Pan; Mingqian Gao; Mingyi Zhang; Jihong Huang (Food Chemistry, 2025)

Experimental and modeling investigation of long-term leachability of nickel in re-molded cement-stabilized sediments - Long Chen; Yong-Hui Chen; Pan-Pan Tang; Wan-Lu Zhang (Environmental Research, 2025)

Dual-function microbial fuel cells: Bioenergy harvesting and microcystin detoxification through molecular docking insights - Yan Liu; Xinli Song; Jia Wei; Yunfeng Pan; Xizi Long; Fei Yang (Journal of Water Process Engineering, 2025)

Identification a novel syntaxin-like protein from silkworm Bombyx mori pathogen Nosema bombycis and characteristics its membrane fusion function - Liuyi Hong; Qing Lv; Hongjie Liao; Zhengkai Xie; Maoping Shao; Yuanyu Zhang; Yuqing Chen; Guoqing Pan; Mengxian Long; Zeyang Zhou (Journal of Invertebrate Pathology, 2025)

Shifts in soil prokaryotic community structure due to clear-cutting secondary Acacia mangium forests and replacing with Eucalyptus urophylla - Yun-Long Zhang; Ning Pan; Wen-Tao Qiao; Richard P. Dick; Dao-Lin Du; Kun Chen; Shan-Shan Qi; Yan Li; Yi Zhou; Yong-Feng Wang (Journal of Environmental Management, 2025)

The microstructural engineering of NiCo2O4 spinel oxides and their catalytic application in methane emission abatement - Cunshuo Li; Shiyi Pan; Wenzhi Li; Nan Zhang; Zhiqin Xu; Jiangtao Hu; Ling Long (Journal of Environmental Chemical Engineering, 2025)

Effect of alternating current electric fields on the preservation of fresh-cut Chinese cabbage and spinach - Wenjing Xiong; Jia Meng; Yuxin Zhang; Guozhi Fan; Cheng Pan; Canduo Shen; Yifei Long (Innovative Food Science & Emerging Technologies, 2025)

Exploration of novel dipeptidyl peptidase-IV inhibitory tetrapeptide from walnut (Juglans sigillata) protein and its effect on diabetes-like phenotypes induced by high-sugar diet in Drosophila melanogaster - Shupeng Chen; Hongyu Pan; Pengtao Huan; Shuguang Wang; Long Sun; Delu Ning; Ting Ma; Yongliang Zhuang (Food Research International, 2025)

Release of multiple elements from food contact materials into a food simulant and potential health risk - Cheng-Zhu Ni; Xiao-Dong Pan; Hai-Tao Shen; Xiao-Min Xu; Jian-Long Han (Food Packaging and Shelf Life, 2025)

Enhanced electron transfer in FeS2-FeMoO4 heterojunction for nearly 100% singlet oxygen generation in efficient water remediation - Dawei Song; Yukun Pan; Huan Chen; Yaqin Shi; Yanan Huang; Bo Niu; Donghui Long; Yayun Zhang (Chemical Engineering Journal, 2025)

Mitochondrial Treatment Improves Cognitive Impairment Induced by Lipopolysaccharide in Mice - Qiu-Qing Yan; Tian-Long Liu; Ling-Ling Liu; Yan-Su Wei; Yuan-Dan Zhao; Chao Yu; Zhen-Guo Zhong; Jin-Lan Huang; Deng-Pan Wu (Molecular Neurobiology, 2025)

Interspecific differences in nitrogen form acquisition strategies contribute to species dominance - Ming Guan; Xiao‐Cui Pan; Jian‐Kun Sun; Ji‐Xin Chen; Xiao‐Lin Wei; Bernhard Schmid; Michel Loreau; Yu‐Long Feng (Ecology, 2025)
Plant's ability to use prevalent or less prevalent soil nitrogen (N) forms may affect their dominance within vegetation types, and these partitioning‐driven changes in dominance may facilitate species co‐existence. However, the mechanisms underlying these processes remain unclear, particularly given the strong influence of altitude on soil N forms, which in turn affect plant N acquisition strategy. In this study, we first determined the effects of preference and plasticity in N form uptake on partitioning of soil N forms and species dominance, and then assessed the relative importance of these two N form use strategies for 19 dominant and non‐dominant species in three vegetation types along an altitudinal gradient on Changbai Mountain, northeast China. To achieve this, we measured dominance, the contents of different N forms in rhizosphere soils, their proportional contributions to leaf N, and N form uptake preference and plasticity for these 19 species. Our results show significant interspecific differences in the proportional contributions of different soil N forms to leaf N within all three vegetation types, providing a novel mechanism underlying niche differentiation among plants. Species dominance was positively associated with the proportional contributions of soil dissolved organic N (the most prevalent N form) and the main inorganic N form to leaf N, while negatively with that of the subordinate inorganic N. These associations were not altered by the altitude‐driven changes in the absolute and proportional contents of different soil N forms, suggesting a potentially widespread phenomenon. Both preference and plasticity in N form uptake contributed to the proportional contributions of different N forms to leaf N, and therefore to species dominance and co‐existence within vegetation types. Furthermore, N form preference was more critical for non‐dominant relative to dominant species and at high relative to low altitude, while N form uptake plasticity was more important for dominant species and at low altitude. Our study provides robust evidence for the interspecific niche differentiation in N form uptake, contributing to species dominance and co‐existence within vegetation types, and reveals the mechanisms (plasticity and preference) underlying the association between species dominance and the uptakes of different N forms.

Corrigendum to “Diffusion of electric vehicles in Beijing considering indirect network effects” [Transport. Res.: Transp. Environ. 127 (2024) 104069] - Lijing Zhu; Wen-Long Shang; Jingzhou Wang; Yixin Li; Chulung Lee; Washington Ochieng; Xunzhang Pan (Transportation Research Part D: Transport and Environment, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

From molecular interactions to foam dynamics: How ionic strength and pH shape egg white protein performance at the air-water interface - Haobo Jin; Sadaqat Ali; Jiajing Pan; Yongguo Jin; Long Sheng (Food Hydrocolloids, 2025)

Oxygen vacancies-enriched CeO2-CoxOy heterostructures facilitate the “trapping-conversion” process of lithium polysulfides for high-performance Li-S batteries - Anran Gao; Qinwen Wu; Hongli Chen; Yukun Pan; Bo Niu; Yayun Zhang; Donghui Long (Chemical Engineering Journal, 2025)

Initial products analysis and mechanistic insights into polystyrene pyrolysis via in-situ photoionization mass spectrometry - Yunqing Zhou; Shi Feng; Hualiang Li; Long Zhao; Zeyou Pan; Zhenzhen Wu; Chuanqi Shi; Zongao Zhen; Zhongyue Zhou; Hao Zhang; Jianhua Yan (Chemical Engineering Journal, 2025)

Simulating the influence of the lake on an extreme precipitation process in the mid-latitude East Asian monsoon fringe region: a case of Chagan Nur Lake - Yue Jing; Long Pan; Ningning Zhang; Yun Shen; Yingqiang Shi; Dandi Liang; Qian Li (Climate Dynamics, 2025)

Estimation of SOC using VNIR and MIR hyperspectral data based on spectral-to-image transforming and multi-channel CNN - Aohua Tang; Guijun Yang; Zhenhong Li; Yuchun Pan; Yu Liu; Huiling Long; Weinan Chen; Jing Zhang; Yue Yang; Xiaodong Yang; Bo Xu (Computers and Electronics in Agriculture, 2025)

FNDC5 alleviates Ox-LDL-induced HUVECs dysfunction by inhibiting ferroptosis through AMPK/Nrf2 signaling - Yipeng Du; Hong Ouyang; Huiyong Wang; Jian Shi; Yuanqing Li; Lingling Xu; Caiyun He; Xiudi Pan; Huidong Long (Tissue and Cell, 2025)

Enhanced vibration dewatering to facilitate efficient disposal process for waste fine flotation tailings - Miao Pan; Tong Xu; Jiawang Lu; Chenlong Duan; Wei Shi; Long Huang; Yidong Shen; Jiale Yuan; Jinpeng Qiao; Haishen Jiang (Minerals Engineering, 2025)

Electrodialysis, a promising approach for nutrients recovery from anaerobic liquid digestate: Status, challenges and perspectives - Xiaofang Pan; Yenan Li; Yahui Huang; Jingwei Xu; Chenyue Sun; Zhi-Long Ye (Journal of Water Process Engineering, 2025)

Deep learning-driven reconstruction of PM2.5 vertical profiles: A fusion of lidar and tower data - Zihuai Yi; Yan Xiang; Long Yun; Xi Mu; Zhenyi Chen; Yuanzhu Dong; Feilong Li; Yin Pan; Lihui Lv; Tianshu Zhang; Wenqing Liu (Journal of Cleaner Production, 2025)

Synergistic generation of ROS via covalent organic frameworks with excellent energy transfer and charge transfer characteristics for phenolic pollutants treatment - Long Zhang; Liujun Yang; Wanyu Wei; Shaoshuo Wang; Yicheng Pan; Yuhan Gu; Liren Gu; Chen Yu; Hua Li; Jianmei Lu (Journal of Environmental Chemical Engineering, 2025)

Cyanobacteria for environmental, energy and biomedical application: a review - Xiaoya Ren; Mengqi Feng; Meiyi Mao; Xizi Long; Jiafeng Pan; Yan Tang; Pengji Zhou; Tangjian Peng; Hui Wang; Fei Yang (Environmental Chemistry Letters, 2025)

Impact of Maternal Exposure to Trace Metal Mixtures on Bone Mineral Density in Children Aged 3–6: Results from the Guangxi Zhuang Birth Cohort, China - Junwang Gu; Huishen Huang; Jun Liang; Qian Liao; Peng Tang; Ying Tang; Jinghua Long; Jiehua Chen; Dongping Huang; Dongxiang Pan; Xiaoyun Zeng; Xiaoqiang Qiu (Biological Trace Element Research, 2025)

Molecular composition difference of electron donating moieties between natural organic matter and effluent organic matter probed by chlorine dioxide - Quan Gao; Yanheng Pan; Yangjian Zhou; Jianglin Peng; Qingqing Kong; Yanhui Cheng; Qing-Long Fu; Xin Yang (Water Research, 2025)

An improved groundwater vulnerability evaluation model based on random forest algorithm and spatio-temporal change prediction method - Bo Li; Pan Wu; Menghua Li; Lixia Chen; Lei Yang; Jie Long (Process Safety and Environmental Protection, 2025)

Effects of reactive oxygen species on fruit ripening and postharvest fruit quality - Wenying Wei; Zesheng Liu; Xuejuan Pan; Tingyue Yang; Caiting An; Yuanhui Wang; Long Li; Weibiao Liao; Chunlei Wang (Plant Science, 2025)

The evolution of sulfur during coalification in marine land interaction environments based on the sequential extraction of different sulfur species - Shuangxue Du; En Long; Yu Qi; Yiwen Ju; Pan Wu; Yong Fu; Shangyi Gu; Hao Zhang; Qingguang Li (Marine and Petroleum Geology, 2025)

Removal of microplastics in sludge during intensive treatment processes in a wastewater treatment plant in China - Huan Li; Wei Pan; Lifen Yao; Lihui An; Long Zhu; Jinhua Gao; Manxiang Wang; Yulin Kang (Journal of Cleaner Production, 2025)

Discovery of Ge2+ in quartz: Evidence from EPR/XAS experiments and DFT calculations, and implications for Ge/Si systematics - Rudolf I. Mashkovtsev; Sanda M. Botis; Jinru Lin; Reza Deevsalar; Leo Ka Long Cheung; Eli Wiens; Ayetullah Tunc; Ning Chen; Roman Chernikov; Yuanming Pan (Geochimica et Cosmochimica Acta, 2025)

Dynamic effects of ultrasonic treatment on flavor and metabolic pathway of pumpkin juice during storage based on GC–MS and GC-IMS - Manjun Zhang; Chunli Zhou; Wei Su; Renqin Tan; Long Ma; Wenhui Pan; Wen Li (Food Chemistry, 2025)

Untargeted metabolomics reveals biochemical changes in wheat by-products during fermentation - Han Li; Long Pan; Xiaoyu Wu; Aimei Liao; Guanghai Yu; Yinchen Hou; Jihong Huang (Food Bioscience, 2025)

Multifunctional Fe3O4@ZIF-8@Ag nanocomposites and electro-driven droplet adsorption strategy for SERS detection of acetamiprid - Xuemei Tang; Wei Zeng; Caiying Wang; Fei Pan; Jing Wei; Long Wu (Chemical Engineering Journal, 2025)

scCrab: A Reference-Guided Cancer Cell Identification Method based on Bayesian Neural Networks - Heyang Hua; Wenxin Long; Yan Pan; Siyu Li; Jianyu Zhou; Haixin Wang; Shengquan Chen (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Exploring the Correlation Between Varied Serum Iodine Nutritional Levels and Anti-Thyroglobulin Antibodies - Qiuyi Song; Tingting Xu; Yu Wang; Hongyan Wei; Feng Tan; Yanting Chen; Fang Fang; Tingkai Cui; Ziyun Pan; Xiaohui Guo; Wen Chen; Jun Shen; et al. (Biological Trace Element Research, 2025)

An improved assessment of the geodetic/seismic deformation in the Southeastern Tibetan Plateau and its implications for regional seismic hazard - Zhengyang Pan; Zhigang Shao; Wuxing Wang; Feng Long; Zhenyu Wang; Meixuan Hao (Tectonophysics, 2025)

Topology optimization of distribution and collection zones for flow field plate of large-scale PEMFC - Congda Xiao; Shaopeng Tian; Hui Guo; Long Wang; Yuxin Pan; Shujin Yang; Wenlong Xie (Fuel, 2025)

Enhancing shelf-life of dried goji berry: Effects of drying methods and packaging conditions on browning evolution - An-An Zhang; Can Shu; Long Xie; Qing-Hui Wang; Ming-Qiang Xu; Yan Pan; Wan-Liang Hao; Zhi-An Zheng; Yu-Hao Jiang; Hong-Wei Xiao (Food Research International, 2025)

Improvement of the gel properties of curdlan gel by hydrogen bonding interaction with trehalose - Long-Qing Li; Le-Yi Pan; Tong-Xin Liang; Mingyu Jin; Ya-Hui Yu; Xiangying Yu; Xiaozhen Liu; Fengyuan Liu; Yuting Li; Jing-Kun Yan (Food Hydrocolloids, 2025)

A novel K57-specific Klebsiella pneumoniae phage disinfects milk and inhibits biofilm formation - Sixiang Xu; Xiaona Yan; Pei Li; Xiaoyue Li; Xiangkuan Zheng; Xiaoxiao Pang; Long Chen; Zihao Pan; Jiale Ma; Xiang Huo; Wei Zhang (Food Control, 2025)

Egg characteristics assessment as an enabler for in-ovo sexing technology: A review - Shaomin Xu; Sifang Long; Zixian Su; Khawar Hayat; Lijuan Xie; Jinming Pan (Biosystems Engineering, 2025)

A novel strategy for improving ammonia resistance of acidogenesis using domesticated sludge combined with nZVI addition in an ambient anaerobic digestion system - Zunjing Lv; Xiaofang Pan; Zhi-Long Ye; Donghua Xie; Guanjing Cai; Nan Lv; Yanlin Li (Water Research, 2025)

Knockdown of the β-N-acetylhexosaminidase genes by RNA interference inhibited the molting and increased the mortality of the white-backed planthopper, Sogatella furcifera - Pan-Pan Guo; Xi-Bin Yang; Hong Yang; Cao Zhou; Gui-Yun Long; Dao-Chao Jin (Pesticide Biochemistry and Physiology, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

Quaternary transgression process controlled by tectonic subsidence over the last 1.35 Ma: New insights from the eastern Bohai Sea - Wei Xiong; Long Huang; Yong Zhang; Zhonglei Wang; Nai Shuang Bi; Jun Pan; Jun Sun; Lelong He; Feifei Wang; Xi Mei (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Bi2O2Se nanosheets coated with rosmarinic acid for colon-targeted treatment of inflammatory bowel disease - Jiahu Yao; Yang Yang; Hu Zhao; Chuanming Wang; Liang Jin; Tengyun Long; Wei Huang; Xiang Zhan; Xin Li; Xin Chen; Jinhu Xie; Bin Wu; et al. (Chemical Engineering Journal, 2025)

The promoted Fenton degradation of norfloxacin by a S-ZnO modified MnFe2O4 with micro-acidic environment - Ting Pan; Danni Wang; Yanyu Song; Yongdi Liu; Long D. Nghiem; Jun Duan; Chengdan Che; Xianbo Sun; Zhengqing Cai (Chemical Engineering Journal, 2025)

An ultrathin conformal layer of dry-coated Li+-conductive glass–ceramic for single-crystalline nickel-rich cathode towards all-solid-state lithium batteries - Yaping Wang; Jianxiang Ding; Xiong Xiong Liu; Mufan Cao; Min Gao; Long Pan; ZhengMing Sun (Chemical Engineering Journal, 2025)

A Microbially Induced Magnesia Carbonation (MIMC) Method with Potential Application for Crack Healing of Sandstone Cultural Relics: Improving Interfacial Bonding Strength - Zhi-Hao Dong; Xiao-Hua Pan; Chao-Sheng Tang; Dian-Long Wang; Rui Wang; Bin Shi (Rock Mechanics and Rock Engineering, 2025)

Insights into human exposure to microplastics through drinking water: Current state of the science - Long Zhu; Wei Pan; Xiaoli Zhao; Feifei Wang; Chen Wang; Yulin Kang; Zhaomin Dong; Bing Shao; Fengchang Wu; Lihui AN (Critical Reviews in Environmental Science and Technology, 2024)

A novel strategy for enhancing high solid anaerobic digestion of fecal slag and food waste using percolate recirculation and dosage of nano zero-valent iron - Hamza Hassan Yusuf; Pan Xiaofang; Zhi-Long Ye; Taha Abdelfattah Mohammed Abdelwahab; Ahmed Elsayed Mahmoud Fodah (Water Research, 2024)

A novel reaction between ammonia and Criegee intermediates can form amines and suppress oligomers from isoprene - Xiaoying Li; Long Jia; Yongfu Xu; Yuepeng Pan (Science of The Total Environment, 2024)

Molecular interaction between ammonium sulfate and secondary organic aerosol from styrene - Shanshan Yu; Long Jia; Yongfu Xu; Yuepeng Pan (Science of The Total Environment, 2024)

Free-radical triggered formation of dioxins from 2-chlorophenol pyrolysis investigated by synchrotron radiation photoionization mass spectrometry - Ming-Gao Xu; Chen Huang; Yi-Fan Zhang; Jia-Bin Huang; Long Zhao; Wenchao Lu; Yang Pan; Jiu-Zhong Yang; Feng Zhang; Zhan-Jun Cheng (Journal of Hazardous Materials, 2024)

Organic matter excreted by the protozoan Tetrahymena thermophila and its effects on the bioaccumulation of nanoparticles - Ke-Da Zhang; Hong-Jie Zhang; Jun-Long Song; Xin-Lei Wang; Wei Pan; Mei Wang; Bin Huang; Liuyan Yang; Ai-Jun Miao (Journal of Hazardous Materials, 2024)

Highly selective separation of 99TcO4−/ReO4− with rapid liquid-liquid two-phase disengagement by amine-diamide ligands - Long Li; Xuanhao Huang; Xiaoyang Hu; Xingyue Liu; Rui Li; Hang Zhou; Fengfeng Li; Fangxiang Luo; Qingjiang Pan; Songdong Ding (Journal of Environmental Chemical Engineering, 2024)

Revealing the key antioxidant compounds and potential action mechanisms of Chinese Cabernet Sauvignon red wines by integrating UHPLC-QTOF-MS-based untargeted metabolomics, network pharmacology and molecular docking approaches - Zhi-Xin Peng; Hui-Wen Gu; Yuan Pan; Yan Wang; Jun Yan; Wanjun Long; Haiyan Fu; Yuanbin She (Food Chemistry, 2024)

Occurrence and risk assessment of coccidiostat residues in chicken meat: A regional study in Southeast China - Hai-Tao Shen; Xiao-Dong Pan; Jian-Long Han (Food Bioscience, 2024)

An efficient bio-stabilization technology with bio‑carbonation of reactive magnesia for soil improvement in cold regions - Rui Wang; Chao-Sheng Tang; Xiao-Hua Pan; Dian-Long Wang; Zhi-Hao Dong; Xiancai Lu (Engineering Geology, 2024)

Maternal Serum Iodine Concentrations in Early Pregnancy Exhibited Well Diagnostic Ability for Thyroid Dysfunction, Inverse Associations with Gestational Weight Gain, and Birth Size: Longitudinal Analyses Based on Huizhou Mother-Infant Cohort - Zhao-min Liu; Huan-huan Long; Dan Li; Ai-ping Fang; Chao-gang Chen; Cheng Wang; Min-min Li; Yi Wu; Su-juan Zhang; Wen-jing Pan (Biological Trace Element Research, 2024)

Ethanol-mediated Anaerobic Digestion: Functional Bacteria and Metabolic Pathways - Doaa Zamel; Xiaofang Pan; Zhi-Long Ye (Chemosphere, 2024)

The effect of Astragalus polysaccharides on the repair of adverse effects in largemouth bass (Micropterus salmoides) under enrofloxacin stress - Xiaoyu Qi; Hongzhou Xu; Jingfei Long; Chenyang Yan; Kuiquan Pan; Yanzhen Song; Xinxin Jiang; Haixia Liu (Aquaculture, 2024)

Insights into the interaction mechanisms between Microcystin-degrading bacteria and Microcystis aeruginosa - Tangjian Peng; Yanqing Tang; Danping Cai; Yuqing Gu; Jia Wei; Jiajia Zhang; Juan Ni; Jun Liu; Xiaoya Ren; Jiafeng Pan; Xizi Long; Hui Wang; et al. (Water Research, 2024)

Detecting topographic effect and urban signature in long-term summer rainfall trend in a complex urban environment - Chengwei Tong; Ruidong Chen; Long Yang; Yi Pan; Qiqi Yuan; Jingsong Ma; Lachun Wang (Urban Climate, 2024)

Effect of valley topography on dynamic response of arch dams - Meng-Zhong Zhang; Yi-Xiang Qiu; Wei-Chi Xu; Jin-Ting Wang; Jian-Wen Pan; Hai-Long Huang (Soil Dynamics and Earthquake Engineering, 2024)

Architecture of the ATP-driven motor for protein import into chloroplasts - Ning Wang; Jiale Xing; Xiaodong Su; Junting Pan; Hui Chen; Lifang Shi; Long Si; Wenqiang Yang; Mei Li (Molecular Plant, 2024)

Association between maternal metal exposure during early pregnancy and intelligence in children aged 3–6 years: Results from a Chinese birth cohort - Junwang Gu; Huishen Huang; Peng Tang; Qian Liao; Jun Liang; Ying Tang; Jinghua Long; Jiehua Chen; Dongping Huang; Shun Liu; Dongxiang Pan; Xiaoyun Zeng; et al. (Environmental Research, 2024)

Microcrystalline-Fe2P4O12 as eco-friendly and efficient anode for high-performance dual-ion battery - Yunbing He; Xuexue Pan; Qingping Long; Hao Yang; Hongkun Huang; Haoxu Zhan; Yiran He; Zhazira Supiyeva; Chao Li; Qamar Abbas (Chemical Engineering Journal, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Potentially toxic element source apportionment and risk assessment in agricultural soils around a large-scale Pb-Zn mine in Southwest China - Heng Wei; Xuekui Niu; Minmin Li; Canwen Cui; Zhonghua Wei; Wei Long; Man Tang; Hong Yu; Peng Zhang; Liping He; Bo Pan (Journal of Environmental Chemical Engineering, 2024)

Preparation of wheat protein peptides-calcium chelate by the ultrasound method: Structural characteristics and bioactivity - Mingyi Zhang; Yinchen Hou; Aimei Liao; Xinyang Chen; Zhen Wang; Penghui Zhao; Long Pan; Jihong Huang (Food Bioscience, 2024)

Determining obstructive or promoting effects of anions and DOM on phosphate transport combining with Donnan dialysis and selective electrodialysis - Yenan Li; Zhi-Long Ye; Natalia Pismenskaya; Xiaofang Pan; Yahui Huang; Semen Mareev; Andrey Gorobchenko (Desalination, 2024)

Deep insights into the enhanced waste active sludge lysis by MoS2 and Fe2+ co-activated persulfate - Ting-Ting Zhang; Zun-Jing Lv; Quan-Bao Zhao; Jia-Cheng E. Yang; Zhi-Long Ye; Xiao-Fang Pan; Yu-Ming Zheng (Chemical Engineering Journal, 2024)

Study on 2-arylbenzo[ b ]furans from Itea omeiensis and their fragmentation patterns with Q-Orbitrap mass spectrometry - Yun-Qian Feng; Pan Zhang; Jin-Zhen Jian; Zhi-Wei Wang; Xiao-Long Tian; Guo-Yong Luo; Wu-De Yang (Natural Product Research, 2024)

Impacts of wastewater treatment plant effluents on dissolved inorganic carbon in highly urbanized karst rivers, Southwest China - Guangxi Long; Y. Jun Xu; Xingxing Cao; Pan Wu; Kai Li (Journal of Hydrology, 2024)

Bioinspired carbon black deposited polyimide fabric for sustainable water energy harvesting - Jianhong Guo; Leyan Zhang; Chunhua Zhang; Dandan Zhong; Weihao Long; Jieyao Qin; Zhuan Fu; Sijie Zhou; Junyao Gong; Heng Pan; Hua Ji; Lixin Du; et al. (Chemical Engineering Journal, 2024)

Molten salt defect engineering regulation of Bi4TaO8Cl perovskite structure for boosting photo-Fenton degradation of antibiotics - Ziwei Guo; Gui Yang; Yang Wu; Juan Long; Huan He; Xiaomin Ren; Bin Huang; Xuejun Pan; Yujun Liang (Chemical Engineering Journal, 2024)

Cu-doped titanium lithium-ion sieves with cell expansion and improved hydrophilicity for efficient extraction of lithium from aqueous resources - Huiqiu Zhang; Bin Dong; Yan Yang; Xin Long; Hangchao Chen; Jinhe Pan; Changchun Zhou (Chemical Engineering Journal, 2024)

Adsorption-desorption of copper(II) by temperature-sensitive nano-biochar@PNIPAM/alginate double-network composite hydrogel: Enhanced mechanisms and application potentials - Haolin Chen; Yiwei Pan; Wei Zhang; Anlin Long; Mengqi Chen; Xinxin Xiao; Ziyi Wang; Meiyi Tang; Yazhou Peng; Shiquan Sun; Huining Zhang; Qiulai He (Chemical Engineering Journal, 2024)

Heat‐stress memory enhances the acclimation of a migratory insect pest to global warming - Peng‐Qi Quan; Pan‐Long Guo; Jing He; Xiang‐Dong Liu (Molecular Ecology, 2024)
In the face of rising global temperatures, the mechanisms behind an organism's ability to acclimate to heat stress remain enigmatic. The rice leaf folder, Cnaphalocrocis medinalis , traditionally viewed as temperature‐sensitive, paradoxically exhibits robust larval acclimation to heat stress. This study used the heat‐acclimated strain HA39, developed through multigenerational exposure to 39°C during the larval stage, and the unacclimated strain HA27 reared at 27°C to unravel the transgenerational effects of heat acclimation and its regulatory mechanisms. Heat acclimation for larvae incurred a fitness cost in pupae when exposed to high temperature, yet a significant transgenerational effect surfaced, revealing heightened fitness benefit in pupae from HA39, even without additional heat exposure during larval recovery at 27°C. This transgenerational effect exhibited a short‐term memory, diminishing after two recovery generations. Moreover, the effect correlated with increased superoxide dismutase (SOD) enzyme activity and expression levels of oxidoreductase genes, representing physiological and molecular foundations of heat acclimation. Heat‐acclimated larvae displayed elevated DNA methylation levels, while pupae from HA39, in recovery generations, exhibited decreased methylation indicated by the upregulation of a demethylase gene and downregulation of two methyltransferase genes at high temperatures. In summary, heat acclimation induces DNA methylation, orchestrating heat‐stress memory and influencing the expression levels of oxidoreductase genes and SOD activity. Heat‐stress memory enhances the acclimation of the migratory insect pest to global warming.

Single-grain luminescence dating of Manas Lake paleoshorelines reveals late quaternary glacial meltwater forced lake level highstand in arid Central Asia - Xiaoyan Wang; Guoqiang Li; He Yang; Yixuan Wang; Ming Jin; Zhongfeng Yan; Caixin Qin; Siyi Gou; Long Pan; Jin Yang (Quaternary Geochronology, 2024)

Optimal emission control plan aiming to basically eliminate PM2.5 heavy pollution in North and Northwest China in 2018 - Zhilan Ye; Long Cheng; Jie Li; Fei Pan; Wenyi Yang; Xueshun Chen; Huiyun Du; Tao Wang; Zhe Wang; Zifa Wang (Journal of Cleaner Production, 2024)

Smart nodding duck: A hybrid Halbach electromagnetic piezoelectric self-powered sensor for smart fisheries - Long Wang; Hongjie Tang; Zutao Zhang; Yajia Pan; Dabing Luo; Bendong Xiong; Tengfei Liu; Congcong Zhang; Hao Wang; Weihua Kong (Chemical Engineering Journal, 2024)

Biochar modulates intracellular electron transfer for nitrate reduction in denitrifying anaerobic methane oxidizing archaea - Pan-Long Lv; Chuan Jia; Chi-Hang Wei; He-Ping Zhao; Rong Chen (Bioresource Technology, 2024)

Exploring the therapeutic efficacy and pharmacological mechanism of Guizhi Fuling Pill on ischemic stroke: a meta-analysis and network pharmacology analysis - Jing Wang; Xinmin Li; Junzi Long; Qian Gao; Mengyang Pan; Fangjie Yang; Yasu Zhang (Metabolic Brain Disease, 2024)

Seismic analysis of gravity dam-foundation systems using stochastic spectral finite element method - Qing-Pei Zeng; Jin-Ting Wang; Meng-Zhong Zhang; Xiang-Chao Wang; Hai-Long Huang; Jian-Wen Pan (Soil Dynamics and Earthquake Engineering, 2024)

Late Holocene decoupling of lake and vegetation ecosystem in response to centennial-millennial climatic changes in arid Central Asia: A case study from Aibi Lake of western Junggar Basin - Long Pan; Guoqiang Li; Chunzhu Chen; Yuanlu Liu; Ji Lai; Jin Yang; Ming Jin; Zhong Wang; Xiaoyan Wang; Weiping Ding (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Associations between maternal exposure to multiple metals and metalloids and blood pressure in preschool children: A mixture-based approach - Jinghua Long; Huishen Huang; Peng Tang; Jun Liang; Qian Liao; Jiehua Chen; Lixiang Pang; Kaiqi Yang; Huanni Wei; Manlin Chen; Xiaolin Wu; Dongping Huang; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

Modulation of molecular state and air-water interface adsorption behavior of ovalbumin via interference with its surrounding charge distribution - Haobo Jin; Jiajing Pan; Yaqin Yang; Yuanyuan Zhang; Yongguo Jin; Long Sheng (Food Hydrocolloids, 2024)

Soil organic carbon storage, microbial abundance and pore structure characteristics of macroaggregates across a soil-landscape sequence in a subtropical hilly watershed - Zheng Zhao; Xiao Feng; Chun Liu; Yue Han; Guogang Long; Shuotong Chen; Qingmei Lin; Jingwen Gong; Yi Shen; Ziyi Mao; Thammavongsa Sounilan; Xuhui Zhang; et al. (CATENA, 2024)

Combining genome-wide association study and linkage mapping in the genetic dissection of amylose content in maize (Zea mays L.) - Wei Dai; Qinglin Li; Tao Liu; Ping Long; Yao He; Mengxiang Sang; Chaoying Zou; Zhong Chen; Guangsheng Yuan; Langlang Ma; Guangtang Pan; Yaou Shen (Theoretical and Applied Genetics, 2024)

Exploring the Impact of Biodegradable and Nonbiodegradable Microplastic Particles on Pb Absorption in Maize - Dan QIU; Chunmiao LU; Huarong SUN; Chaohang LI; Guangqiang LONG; Ping ZHAO; Yijun LONG; Yue DING; Cuixia SU; Zhengyan PAN; Yuefang CAO; Shuran HE (Journal of Soils and Sediments, 2024)

Adaptation of a prey population to increasing predation risks - Ling Pan; Han Zhu; Yan Wang; Bao-Chun Shi; Xin-Feng Cheng; Ya-Li Ge; Xian-Ling Xiang; Xin-Li Wen; Yi-Long Xi (Hydrobiologia, 2024)

Effects of equatorial plasma bubble-induced ionospheric gradients on GNSS PPP-RTK - Long Tang; Fenkai Zhang; Pan Li; Yuanfan Deng; Wu Chen (GPS Solutions, 2024)
Equatorial plasma bubble (EPB) exerts a severe threat to global navigation satellite system (GNSS) technique. It not only can lead to ionospheric scintillation, but also can create strong plasma gradients in ionosphere. In this study, we investigate the effects of EPB-induced ionospheric gradients on GNSS precise point positioning with real-time kinematic (PPP-RTK) technique for the first time. A common medium-scale EPB event occurred in ionosphere over the southern U.S. on May 28, 2017 is served as a case. The results show, during the period of the EPB event, the interpolated ionospheric residuals are very large with maximum 7.5 TECU without EPB correction while the counterparts are generally below 1 TECU with EPB correction. As for the 3D positions, EPB-induced ionospheric gradients mainly affect the initialization or re-initialization process of PPP-RTK solutions, which significantly increase the estimated errors and lengthen the convergence times. This study can help the GNSS community understand EPB’s impacts on GNSS PPP-RTK more deeply and provide support for its mitigation in the next work.

Temperature-Dependent NiFeAl catalysts for efficient microwave-assisted catalytic pyrolysis of polyethylene into value-added hydrogen and carbon nanotubes - Zhe Zhang; Huan Chen; Wenheng Hu; Meng Xie; Yukun Pan; Bo Niu; Dengle Duan; Lu Ding; Donghui Long; Yayun Zhang (Fuel, 2024)

Effect of the ripening stage on the pulsed vacuum drying behavior of goji berry (Lycium barbarum L.): Ultrastructure, drying characteristics, and browning mechanism - An-An Zhang; Long Xie; Qing-Hui Wang; Ming-Qiang Xu; Yan Pan; Zhi-An Zheng; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2024)

Dissolved carbon in effluent of wastewater treatment plants and its potential impacts in the receiving karst river - Xingxing Cao; Y. Jun Xu; Guangxi Long; Pan Wu; Zhangxing Liu (Environmental Research, 2024)

Shock-endurable and reversible evolution between CoOOH and intermediate governed by interfacial strain for fluctuating oxygen evolution - Hongxia Yin; Lihua Qian; Hengbo Xiao; Long Zhang; Ximin Li; Xiangji Zhou; Songliu Yuan; Canglong Li; Qiuhong Lu; Fei Pan; Liqing Zeng; Junjie Guo; et al. (Chemical Engineering Journal, 2024)

Imperceptible liquid metal based tattoo for Human-Machine interface on hairy skin - Weikang Lin; Liqing Ai; Yuanyi Wang; Xiaodan Yang; Junchen Liao; Qiqi Pan; Ying Hong; Shiyuan Liu; Zhihe Long; Bee Luan Khoo; Xi Yao; Zhengbao Yang (Chemical Engineering Journal, 2024)

Enhancing electrokinetic remediation of soil contaminated with As, Cd, Cu, and Pb using the biodegradable chelator GLDA: A pilot study - Zhiwei Pan; Genmei Wang; Jiaqi Liang; Long Cang (Journal of Soils and Sediments, 2024)

Sugarcane borers: species, distribution, damage and management options - Ao-Mei Li; Zhong-Liang Chen; Fen Liao; Yong Zhao; Cui-Xian Qin; Miao Wang; You-Qiang Pan; Shao-Long Wei; Dong-Liang Huang (Journal of Pest Science, 2024)
Lepidopteran borers stand out as the most destructive pests in sugarcane, leading to reductions in stalk weight, juice quality and sugar recovery. Presently, integrated pest management (IPM) systems are utilized for sugarcane borer management, employing diverse methods encompassing cropping system, chemical pesticides, behavioral manipulation, biological agents and the selection of resistant varieties. However, the effectiveness of this strategy remains controversial due to concerns about harmful residues, formulation limitations, environmental variability, labor shortages and increased input costs. Currently, multiple lines of transgenic sugarcane expressing insecticidal genes from the bacterium Bacillus thuringiensis (Bt) have been developed globally, offering the prospect of increases production with reduced pesticides application, thereby eliminating the negative effect of IPM. In Brazil, the first genetically modified sugarcane cultivars resistant to the sugarcane borer have been approved and released for commercial cultivation, shedding a bright light on a viable solution for sugarcane borers. This paper reviews borer species and distribution, the significant damage caused by sugarcane borers, current control approaches and the future effective control strategies. Additionally, this work provides comprehensive understanding on Bt sugarcane, serving as an additional tool to complement conventional sugarcane borers control resistance programs.

Evaluation of Opaque-2 effects on popping characteristics using iTRAQ-based proteome profiles in popcorn - Yongbin Dong; Qi Zheng; Junjie Zhu; Qingling Shi; Siqi Jiang; Mengying Pan; Xinyue Zhang; Long Zhang; Yuling Li (Euphytica, 2024)

Genetic correlation and causal associations between circulating C-reactive protein levels and lung cancer risk - Jiajun Shi; Wanqing Wen; Jirong Long; Haoran Xue; Yaohua Yang; Ran Tao; Wei Pan; Xiao-Ou Shu; Qiuyin Cai (Cancer Causes & Control, 2024)

Application and Comparison of Different Regression Models in Iodine Balance Experiment on Women of Childbearing Age and Pregnant Women - Yu Wang; Xiaoxiao Tian; Qiuyi Song; Wenqiang Wang; Xiaohui Guo; Tingkai Cui; Ziyun Pan; Yongjie Chen; Wen Chen; Long Tan; Wanqi Zhang (Biological Trace Element Research, 2024)

Reference Intervals of Serum Iodine Concentration in Chinese Pregnant Women - Yi Wu; Huan-huan Long; Su-juan Zhang; Min-Min Li; Chao-gang Chen; Cheng Wang; Zheng-yu Sheng; Yan-bin Ye; Shu-yu Zuo; Wen-jing Pan; Zhao-min Liu (Biological Trace Element Research, 2024)

Correction: Spontaneous mutations and mutational responses to penicillin treatment in the bacterial pathogen Streptococcus pneumoniae D39 - Wanyue Jiang; Tongtong Lin; Jiao Pan; Caitlyn E. Rivera; Clayton Tincher; Yaohai Wang; Yu Zhang; Xiang Gao; Yan Wang; Ho-Ching T. Tsui; Malcolm E. Winkler; Michael Lynch; et al. (Marine Life Science & Technology, 2024)

Assessing the hepatotoxicity of phosphogypsum leachate in zebrafish (Danio rerio) - Min Wang; Ziyu Guo; Jiangfeng Du; Hongliang Lu; Long Liu; Tao Wang; Sha Pan (Science of The Total Environment, 2024)

Microplastics derived from plastic mulch films and their carrier function effect on the environmental risk of pesticides - Xin Bao; Yuntong Gu; Long Chen; Zijian Wang; Hui Pan; Shiran Huang; Zhiyuan Meng; Xiaojun Chen (Science of The Total Environment, 2024)

Multifunctional self-assembled adsorption microspheres based on waste bamboo shoot shells for multi-pollutant water purification - Jie Yang; Qianxin Long; Yan Zhu; Cheng Lin; Xiaoxi Xu; Baiyang Pan; Wenya Shi; Yuyang Guo; Jianqiu Deng; Qingrong Yao; Zhongmin Wang (Environmental Research, 2024)

DNAL7, a new allele of NAL11, has major pleiotropic effects on rice architecture - Jie Wang; Weixiong Long; Jintao Pan; Xiaolin Zhang; Lihua Luo; Mingjuan Qian; Wei Chen; Laiyang Luo; Weibiao Xu; Yonghui Li; Yaohui Cai; Hongwei Xie (Planta, 2024)

Social parasitism behavior between two species of edible wasps in China - Cheng-Ye Wang; Hao-Yu Chen; Bing-Qing Fang; Pan-Li Yang; Zhao He; Long Sun; Jin Gan; Min Zhao; Ying Feng (Journal of Ethology, 2024)

KDELR2 promotes bone marrow mesenchymal stem cell osteogenic differentiation via GSK3β/β-catenin signaling pathway - Xiaoyong Wu; Weijun Zhang; Long Long; Yibo Wang; Hongyu Chen; Kanbin Wang; Zhongxiang Wang; Jinwu Bai; Deting Xue; Zhijun Pan (Cell and Tissue Research, 2024)

Spontaneous mutations and mutational responses to penicillin treatment in the bacterial pathogen Streptococcus pneumoniae D39 - Wanyue Jiang; Tongtong Lin; Jiao Pan; Caitlyn E. Rivera; Clayton Tincher; Yaohai Wang; Yu Zhang; Xiang Gao; Yan Wang; Ho-Ching T. Tsui; Malcolm E. Winkler; Michael Lynch; et al. (Marine Life Science & Technology, 2024)
Bacteria with functional DNA repair systems are expected to have low mutation rates due to strong natural selection for genomic stability. However, our study of the wild-type Streptococcus pneumoniae D39, a pathogen responsible for many common diseases, revealed a high spontaneous mutation rate of 0.02 per genome per cell division in mutation-accumulation (MA) lines. This rate is orders of magnitude higher than that of other non-mutator bacteria and is characterized by a high mutation bias in the A/T direction. The high mutation rate may have resulted from a reduction in the overall efficiency of selection, conferred by the tiny effective population size in nature. In line with this, S. pneumoniae D39 also exhibited the lowest DNA mismatch-repair (MMR) efficiency among bacteria. Treatment with the antibiotic penicillin did not elevate the mutation rate, as penicillin did not induce DNA damage and S. pneumoniae lacks a stress response pathway. Our findings suggested that the MA results are applicable to within-host scenarios and provide insights into pathogen evolution.

Opportunities and challenges of polyphenols and polysaccharides for type 1 diabetes intervention - Binbin Li; Li-Long Pan; Xiaohua Pan; Xiaoliang Dong; Zhengnan Ren; Hao Zhang; Wei Chen; Paul de Vos; Jia Sun (Critical Reviews in Food Science and Nutrition, 2024)

Understanding the route choice preferences of private and dock-based public bike users using GPS data in Seoul, South Korea - Jaehoon Chung; Enjian Yao; Long Pan; Joonho Ko (Journal of Transport Geography, 2024)

Effects of climate and geochemical properties on the chemical forms of soil Cd, Pb and Cr along a more than 4000 km transect - Zhiqiang Bai; Ting Li; Shirong Zhang; Guiyin Wang; Xiaoxun Xu; Wei Zhou; Xiaomei Pan; Yulin Pu; Yongxia Jia; Zhanbiao Yang; Lulu Long (Journal of Hazardous Materials, 2024)

A critical review on metallurgical recovery of iron from iron ore tailings - Hailin Long; Deqing Zhu; Jian Pan; Siwei Li; CongCong Yang; Zhengqi Guo; Xianqing Xu (Journal of Environmental Chemical Engineering, 2024)

Rolling forms the diversities of small molecular nonvolatile metabolite profile and consequently shapes the bacterial community structure for Keemun black tea - Zhi-Wei Ren; Hong-Jing Pan; Cheng Hu; Miao-Miao Le; Yan-Hua Long; Qian Xu; Zhong-Wen Xie; Tie-Jun Ling (Food Research International, 2024)

The effect of triclosan on intergeneric horizontal transmission of plasmid-mediated tigecycline resistance gene tet(X4) from Citrobacter freundii isolated from grass carp gut - Xinxin Jiang; Jingfei Long; Yanzhen Song; Xiaoyu Qi; Ping Li; Kuiquan Pan; Chenyang Yan; Hongzhou Xu; Haixia Liu (Environmental Pollution, 2024)

Weakening the integrity of waxy starch granules by selective degradation of amorphous matrices using gaseous hydrogen chloride - Chia-Long Lin; Jheng-Hua Lin; Ciao-Ling Pan; Yung-Ho Chang (Carbohydrate Polymers, 2024)

Contrasting moist heat across local climate zones in heat and non-heat waves: Insights from 29 Chinese metropolises - Sida Jiang; Wenfeng Zhan; Long Li; Chunli Wang; Pan Dong; Shasha Wang; Yingying Ji; Fan Huang; Zihan Liu; Yihan Gao (Building and Environment, 2024)

Regional climate model intercomparison over the Tibetan Plateau in the GEWEX/LS4P Phase I - Jianping Tang; Yongkang Xue; Mengyuan Long; Mengnan Ma; Xin-Zhong Liang; Shiori Sugimoto; Kun Yang; Zhenming Ji; Jinkyu Hong; Jeongwon Kim; Haoran Xu; Xu Zhou; et al. (Climate Dynamics, 2024)

Antibiotic residues in commercial freshwater fish from southeast China: distribution and human health risk assessment - Guo-Jian Shao; Xiao-Dong Pan; Jian-Long Han (Environmental Science and Pollution Research, 2024)

Influence paradigms of soil moisture on land surface energy partitioning under different climatic conditions - Xiao Chen; Zhihua Pan; Binxiang Huang; Ju Liang; Jialin Wang; Ziyuan Zhang; Kang Jiang; Na Huang; Guolin Han; Buju Long; Zhenzhen Zhang; Jingyu Men; et al. (Science of The Total Environment, 2024)

Recent advances on beneficial management of lithium refinery residue in China - Jihua Zhai; Pan Chen; Jianping Long; Changyi Fan; Zhiyong Chen; Wei Sun (Minerals Engineering, 2024)

Efficient perchlorate reduction in microaerobic environment facilitated by partner methane oxidizers - Pan-Long Lv; Chuan Jia; Chi-Hang Wei; He-Ping Zhao; Rong Chen (Journal of Hazardous Materials, 2024)

Monospecific and ultrasensitive detection of ofloxacin: A computational chemistry-assisted hapten screening strategy and analysis of molecular recognition mechanism - Jiaxu Xiao; Liangni Qin; Dan Zhao; Niexie Huang; Wennuo Xu; Linwei Zhang; Xiaoming Pan; Shiyun Han; Mingyue Ding; Long Li; Tao Le; Dapeng Peng (Journal of Hazardous Materials, 2024)

The response of riverine Mg isotope to hydrology and implications for continental weathering - Long Ma; Kang-Jun Huang; Pan Zhang; Zhangdong Jin; Yan Zhao; Yuanqiang Guo (Geochimica et Cosmochimica Acta, 2024)

Sulfide compositions of young Chang’e-5 basalts and implications for sulfur isotopes in lunar basalt sources - Zaicong Wang; Yiheng Li; Wen Zhang; Qi He; Fabin Pan; Zhaochu Hu; Keqing Zong; Yantong Feng; Harry Becker; James M.D. Day; Wenlei Song; Hejiu Hui; et al. (Geochimica et Cosmochimica Acta, 2024)

Highly efficient solution-processable four-coordinate boron compound: A thermally activated delayed fluorescence emitter with short-lived phosphorescence for OLEDs with small efficiency roll-off - Zhengqin Pan; Jie Pan; Long Sang; Zhenming Ding; Meihua Liu; Laichao Fu; Mengqiu Wang; Xiaokang Huang; Bowen Li; Shaofeng Chen; Dongcheng Chen; Yu Liu; et al. (Chemical Engineering Journal, 2024)

Oligomer formation from cross-reaction of Criegee intermediates in the styrene-isoprene-O3 mixed system - Shanshan Yu; Long Jia; Yongfu Xu; Yuepeng Pan (Chemosphere, 2024)

Ecytonucleospora hepatopenaei proliferate in Procambarus clarkii: A warning for crayfish and shrimp aquaculture - Bingxin Ling; Yujiao Wu; Qing Yu; Chunxia Wang; Mengjiao Hu; Xianzhi Meng; Mengxian Long; Guoqing Pan; Zhonghuai Xiang; Zeyang Zhou; Jie Chen (Aquaculture, 2024)

Effect of dietary iron (Fe) level on growth performance and health status of largemouth bass (Micropterus salmoides) - Xiangjie Mao; Wangwang Chen; Xianmei Long; Xiaomei Pan; Guoqing Liu; Wenguang Hu; Dianchao Gu; Qingsong Tan (Aquaculture, 2024)

Diffusion of electric vehicles in Beijing considering indirect network effects - Lijing Zhu; Wen-Long Shang; Jingzhou Wang; Yixin Li; Chulung Lee; Washington Ochieng; Xunzhang Pan (Transportation Research Part D: Transport and Environment, 2024)

Ecological impact of surfactant Tween-80 on plankton: High-scale analyses reveal deeper hazards - Duanyang Yuan; Yaoyue Long; Dan Liu; Fangjie Zhou; Change Liu; Liqiang Chen; Ying Pan (Science of The Total Environment, 2024)

Revolutionizing sanitation: Valorizing fecal slags through co-digesting food waste at high-solid content and dosing metallic nanomaterials for anaerobic digestion stability - Hamza Hassan Yusuf; Xiaofang Pan; Zhi-Long Ye; Guanjing Cai; Lise Appels; Jiasheng Cai; Zunjing Lv; Yanlin Li; Jing Ning (Journal of Environmental Management, 2024)

UHPLC-QTOF-MS-based untargeted metabolomic authentication of Chinese red wines according to their grape varieties - Xiao-Li Yin; Zhi-Xin Peng; Yuan Pan; Yi Lv; Wanjun Long; Hui-Wen Gu; Haiyan Fu; Yuanbin She (Food Research International, 2024)

A Novel Functional Compatibilization Strategy for Poly(lactic acid) and Poly(butylene adipate-co-butylene terephthalate) Blends to Achieve a Stable Co-continuous Structure and Excellent Antibacterial Performance - Lei Sun; Yang Long; Tingyan Peng; Xiaowen Xie; Xianglei Meng; Khian-Hooi Chew; Zhijun Zhang; Zhifeng Dai; Qiangbiao Pan; Yubing Xiong (Chemical Engineering Journal, 2024)

Study on modes of occurrence and selective leaching of lithium in coal gangue via grinding-thermal activation - Hangchao Chen; Lei Zhang; Jinhe Pan; Xin He; Shulan Shi; Xin Long; Yan Yang; Xindi Zhao; Changchun Zhou (Chemical Engineering Journal, 2024)

Removal of toxic metals using iron sulfide particles: A brief overview of modifications and mechanisms - Vaishali Sharma; Ruixin Yan; Xiuping Feng; Junqing Xu; Meitian Pan; Long Kong; Liang Li (Chemosphere, 2024)

Identification of inducible CYP3 and CYP4 genes associated with abamectin tolerance in the fat body and Malpighian tubules of Spodoptera litura - Lin Liang; Jianyi Li; Long Jin; Kunpeng Yan; Yiou Pan; Qingli Shang (Pesticide Biochemistry and Physiology, 2024)

Dietary shifts drive the slowdown of declining methylmercury related health risk in China - Yumeng Li; Qiumeng Zhong; Pan He; Long Chen; Haifeng Zhou; Xiaohui Wu; Sai Liang (Environmental Pollution, 2024)

Online and in-situ monitoring of the growth of silver nanowires and nanoparticles with conductive measurement - Huangqing Ye; Xuchao Jian; Ying Wang; Jun Long; Xiaofang Zhang; Junqin Wu; Yingying Pan; Yu Wang; Xiping Zeng; Xian-Zhu Fu; Jing-Li Luo (Chemical Engineering Journal, 2024)

Enhancing Zn2+ diffusion for dendrite-free zinc anodes via a robust zincophilic clay mineral coating - Mengjiao Liu; Anjun Hu; Zhongfu Yan; Jiahao Chen; Miao He; Bo Zhou; Yu Pan; Yining Fan; Daojiang Gao; Jianping Long (Chemical Engineering Journal, 2024)

Microbial stratification protects denitrifying anaerobic methane oxidation archaea and bacteria from external oxygen shock in membrane biofilm reactor - Pan-Long Lv; Chuan Jia; Xu Guo; He-Ping Zhao; Rong Chen (Bioresource Technology, 2024)

Potentiation of the lateral habenula-ventral tegmental area pathway underlines the susceptibility to depression in mice with chronic pain - Chun-Kui Zhang; Pan Wang; Yuan-Yuan Ji; Jian-Shuai Zhao; Jun-Xiang Gu; Xian-Xia Yan; Hong-Wei Fan; Ming-Ming Zhang; Yu Qiao; Xiao-Die Liu; Bao-Juan Li; Ming-Hui Wang; et al. (Science China Life Sciences, 2024)

Simvastatin ameliorates synaptic plasticity impairment in chronic mild stress-induced depressed mice by modulating hippocampal NMDA receptor - Xu-Ben Yu; Kai-Long Zhong; Chuang Chen; Jing Fu; Fang Chen; Hong-Min Zhou; Xiu-Hua Zhang; Kwonseop Kim; Jing-Ye Pan (Psychopharmacology, 2024)

Micro-interaction of montmorillonite-loaded nanoparticles with mucin promotes retention of betaxolol hydrochloride on the ocular surface and the tear film microenvironment - Yingshan Zhao; Jie Hu; Yuancheng Ke; Qinqiang Long; Jinlan Mao; Huihui Li; Zhenping Xiao; Kangyiran Pan; Siying Yuan; Jiayi Xue; Wei Li; Meiju Zhong; et al. (Applied Clay Science, 2024)

Therapeutic efficacy and pharmacological mechanism of Yindan Xinnaotong soft capsule on acute ischemic stroke: a meta-analysis and network pharmacology analysis - Fangjie Yang; Xinmin Li; Junzi Long; Qian Gao; Mengyang Pan; Jing Wang; Yasu Zhang (Metabolic Brain Disease, 2023)

White rice consumption and risk of cardiometabolic and cancer outcomes: A systematic review and dose-response meta-analysis of prospective cohort studies - Honghao Lai; Mingyao Sun; Yafei Liu; Hongfei Zhu; Mengting Li; Bei Pan; Qi Wang; Qiuyu Yang; Xiao Cao; Chen Tian; Yao Lu; Xuping Song; et al. (Critical Reviews in Food Science and Nutrition, 2023)

How accompanying ions affect soil heavy metal removal by polyepoxysuccinic acid during washing? - Qinmei Zhong; Shirong Zhang; Ting Li; Guoshu Gong; Xiaoxun Xu; Guiyin Wang; Xiaomei Pan; Wei Zhou; Yulin Pu; Lulu Long; Shengtao Yang; Yue Yuan (Chemosphere, 2023)

Jujube quality grading using a generative adversarial network with an imbalanced data set - Hao Cang; Tianying Yan; Long Duan; JingKun Yan; Yuan Zhang; Fei Tan; Xin Lv; Pan Gao (Biosystems Engineering, 2023)

HLEL: A wetland classification algorithm with self-learning capability, taking the Sanjiang Nature Reserve I as an example - Wenhan Jiang; Meng Zhang; Jiangping Long; Yulin Pan; Yimin Ma; Hui Lin (Journal of Hydrology, 2023)

Transport of pollutants in groundwater of domestic waste landfills in karst regions and its engineering control technologies - Bo Li; Teng Li; Pan Wu; Lei Yang; Jie Long; Pu Liu; Tao Li (Journal of Environmental Management, 2023)

Hepcidin from Onychostoma macrolepis: Response to Aeromonas hydrophila infection by down-regulating expression of inflammatory factor genes and regulating iron homeostasis potentially - Kuiquan Pan; Hongzhou Xu; Chenyang Yan; Jun Chen; Xinxin Jiang; Yanzhen Song; Xiaoyu Qi; Jingfei Long; Haixia Liu (Fish & Shellfish Immunology, 2023)

Manipulating Li2O2 deposition morphology by surface spin modulation of cobalt-based spinel oxide catalysts in lithium−oxygen batteries - Yu Pan; Kun Li; Anjun Hu; Chuan Zhao; Yiming Zhang; Xiaoping Jiang; Baihai Li; Jun Wang; Jianping Long (Chemical Engineering Journal, 2023)

Exploration of the Catalytic Cycle Dynamics of Vigna Radiata H+–Translocating Pyrophosphatases Through Hydrogen–Deuterium Exchange Mass Spectrometry - Li-Kun Huang; Yi-Cyuan Huang; Pin-Chuan Chen; Ching-Hung Lee; Shih-Ming Lin; Yuan-Hao Howard Hsu; Rong-Long Pan (The Journal of Membrane Biology, 2023)

Genetic spectrums and clinical profiles of critically ill neonates with congenital auricular deformity in the China Neonatal Genomes Project - Feifan Xiao; Bingbing Wu; Chenbin Dong; Guoqiang Cheng; Yun Cao; Laishuan Wang; Xinran Dong; Yulan Lu; Lin Yang; Liping Chen; Long Li; Xinnian Pan; et al. (Human Genetics, 2023)

Clinical comprehensive evaluation of direct oral anticoagulants for patients with atrial fibrillation in China - Chi Zhang; Zhi-Chun Gu; Er-Li Ma; Bing-Long Liu; Mang-Mang Pan; Jia Wang; Xin Wang; Bin Wu; Hou-Wen Lin (European Journal of Clinical Pharmacology, 2023)

Simple yet efficient downscaling of land surface temperatures by suitably integrating kernel- and fusion-based methods - Pan Dong; Wenfeng Zhan; Chenguang Wang; Sida Jiang; Huilin Du; Zihan Liu; Yangyi Chen; Long Li; Shasha Wang; Yingying Ji (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Proteomic characterization of extracellular vesicles derived from lactic acid bacteria - Bao-Hong Lee; You-Zuo Chen; Tang-Long Shen; Tzu-Ming Pan; Wei-Hsuan Hsu (Food Chemistry, 2023)

Growth mechanism and structure regulation of super-elastic SiC aerogels for thermal insulation and electromagnetic wave absorption - Mingyuan Yan; Xudong Cheng; Lunlun Gong; Zhiyi Lun; Pan He; Long Shi; Chenjie Liu; Yuelei Pan (Chemical Engineering Journal, 2023)

Rapid adaptation of a rotifer prey population to non-consumptive predation pressures - Ling Pan; Han Zhu; Yi-Long Xi; Xin-Feng Cheng; Ya-Li Ge; Xian-Ling Xiang; Xin-Li Wen (Hydrobiologia, 2023)

Quality assessment of the ionospheric density profiles based on long-term COSMIC 1 and 2 radio occultation observations - Na Fu; Rui Zhang; Qixin Pan; Xiaojing Tian; Shaoqiu Long; Chaolong Yao (Journal of Earth System Science, 2023)

Mechanism of Pd(II) adsorption by nanoscale titanium dioxide loaded bamboo shoot shell biomass - Jie Yang; Songlin Liu; Xiaoxi Xu; Baiyang Pan; Qianxin Long; Lichun Cheng; Jianqiu Deng; Qingrong Yao; Zhao Lu; Zhongmin Wang; Huaiying Zhou (Environmental Science and Pollution Research, 2023)

Direct immobilization of Se(IV) from acidic Se(IV)-rich wastewater via ferric selenite Co-precipitation - Zidan Yuan; Rui Su; Xu Ma; Le Yu; Yuanming Pan; Ning Chen; Roman Chernikov; Leo Ka Long Cheung; Reza Deevsalar; Ayetullah Tunc; Liang Wang; Xiangfeng Zeng; et al. (Journal of Hazardous Materials, 2023)

Efficient 2-O-α-D-glucopyranosyl-sn-glycerol production by single whole-cell biotransformation through combined engineering and expression regulation with novel sucrose phosphorylase from Leuconostoc mesenteroides ATCC 8293 - Peifeng Duan; Mengfei Long; Xian Zhang; Zuyi Liu; Jiajia You; Xuewei Pan; Weilai Fu; Meijuan Xu; Taowei Yang; Minglong Shao; Zhiming Rao (Bioresource Technology, 2023)

Contribution of the SOS response and the DNA repair systems to norfloxacin induced mutations in E. coli - Tongtong Lin; Jiao Pan; Colin Gregory; Yaohai Wang; Clayton Tincher; Caitlyn Rivera; Michael Lynch; Hongan Long; Yu Zhang (Marine Life Science & Technology, 2023)
Antibiotic-resistant bacteria severely threaten human health. Besides spontaneous mutations generated by endogenous factors, the resistance might also originate from mutations induced by certain antibiotics, such as the fluoroquinolones. Such antibiotics increase the genome-wide mutation rate by introducing replication errors from the SOS response pathway or decreasing the efficiency of the DNA repair systems. However, the relative contributions of these molecular mechanisms remain unclear, hindering understanding of the generation of resistant pathogens. Here, using newly-accumulated mutations of wild-type and SOS-uninducible Escherichia coli strains, as well as those of the strains deficient for the mismatch repair (MMR) and the oxidative damage repair pathways, we find that the SOS response is the major mutagenesis contributor in mutation elevation, responsible for ~ 30–50% of the total base-pair substitution (BPS) mutation-rate elevation upon treatment with sublethal levels of norfloxacin (0 ~ 50 ng/mL). We further estimate the significance of the effects on other mutational features of these mechanisms (i.e., transversions, structural variations, and mutation spectrum) in E. coli using linear models. The SOS response plays a positive role in all three mutational features (mutation rates of BPSs, transversions, structural variations) and affects the mutational spectrum. The repair systems significantly reduce the BPS mutation rate and the transversion rate, regardless of whether antibiotics are present, while significantly increasing the structural variation rate in E. coli . Our results quantitatively disentangle the contributions of the SOS response and DNA repair systems in antibiotic-induced mutagenesis.

Reducing carbon footprints and increasing net ecosystem economic benefits through dense planting with less nitrogen in double-cropping rice systems - Wentao Zhou; Wenfei Long; Hongrui Wang; Pan Long; Ying Xu; Kangyu Zhong; Rui Xiong; Feipeng Xie; Fugui Chen; Zhiqiang Fu (Science of The Total Environment, 2023)

Onset time and accretionary formation of Mollisols in Northeast China - Fei Yang; Hao Long; Keyang Gong; Yonghui Shi; Jingran Zhang; Aimin Zhang; Na Yang; Peng Cheng; Xumin Pan; Ganlin Zhang (Science Bulletin, 2023)

Halide perovskite-based tribovoltaic effects for self-powered sensors - Yinghui Wu; Long-Biao Huang; Caofeng Pan (Science Bulletin, 2023)

Bioinspired microenvironment modulation of metal–organic framework-based catalysts for selective methane oxidation - Jianfei Sui; Ming-Liang Gao; Bing Qian; Chengyuan Liu; Yang Pan; Zheng Meng; Daqiang Yuan; Hai-Long Jiang (Science Bulletin, 2023)

The relationship between perfluoroalkyl substances and hypertension: A systematic review and meta-analysis - Kai Pan; Jie Xu; Xianping Long; Lilin Yang; Zhiyu Huang; Jie Yu (Environmental Research, 2023)

Constructing bifunctional porous nanosheets for efficient conversion of waste plastics into valuable hydrogen and carbons - Meng Xie; Hai Xu; YiXuan Wang; Helin Pan; Dengle Duan; Bo Niu; Donghui Long; Yayun Zhang (Chemical Engineering Journal, 2023)

Full life circle of micro-nano bubbles: Generation, characterization and applications - Jianguang Jia; Zhaoxu Zhu; Hao Chen; Hongyu Pan; Long Jiang; Wen-Hao Su; Qiang Chen; Yingwen Tang; Jianming Pan; Kai Yu (Chemical Engineering Journal, 2023)

An aminocaproic acid-grafted chitosan derivative with superior antibacterial and hemostatic properties for the prevention of secondary bleeding - Xiao-Juan Chen; Zhi-Yong Lei; Pan Liu; Meng-Jie Lei; Hang Xu; Long-Jiang Yu; Ming-Zhang Ao (Carbohydrate Polymers, 2023)

Bacterial antioxidant mechanism in calcium peroxide aided sludge anaerobic fermentation - Li Liu; Yu Pan; Xiaohan Zhi; Long Chen; Hongtao Zhu (Bioresource Technology, 2023)

Effects of substrate on burrowing behavior, feeding physiology, and energy budget of undulated surf clam Paphia undulata - Pengfei Zhang; Edwine Yongo; Fei Liu; Shuai Pan; Anfu Sun; Long Zhou; Zhiqiang Guo; Caihuan Ke (Journal of Oceanology and Limnology, 2023)

An integrative protocol for one-step PCR amplicon library construction and accurate demultiplexing of pooled sequencing data - Jiahao Ni; Jiao Pan; Yaohai Wang; Tianhao Chen; Xinshi Feng; Yichen Li; Tongtong Lin; Michael Lynch; Hongan Long; Weiyi Li (Marine Life Science & Technology, 2023)

Global mapping of urban thermal anisotropy reveals substantial potential biases for remotely sensed urban climates - Huilin Du; Wenfeng Zhan; Zihan Liu; E. Scott Krayenhoff; TC Chakraborty; Lei Zhao; Lu Jiang; Pan Dong; Long Li; Fan Huang; Shasha Wang; Yuyue Xu (Science Bulletin, 2023)

Identification and functional study of detoxification-related genes in response to tolfenpyrad stress in Glyphodes pyloalis Walker (Lepidoptera: Pyralidae) - Xin Pan; Jian-Hao Ding; Shuai-Qi Zhao; Hui-Cong Shi; Wang-Long Miao; Fu-An Wu; Sheng Sheng; Wei-Hong Zhou (Pesticide Biochemistry and Physiology, 2023)

Homoacetogenesis is altering the metabolic pathway of acidogenic microbiome and combating volatile fatty acid accumulation in anaerobic reactors - Zunjing Lv; Xiaofang Pan; Zhi-Long Ye; Irini Angelidaki; Nan Lv; Yanlin Li; Guanjing Cai; Lifeng Lin (Journal of Environmental Chemical Engineering, 2023)

Rockfall feature investigation and kinematic simulation based on nap-of-the-object photogrammetry and GIS spatial modeling - Xude Li; Fu-zhen Liu; Li Zhao; Na Deng; Long Chen; Jing-shen Pan; Guo-qiang Tang (Natural Hazards, 2023)

Correction to: Global honeybee health decline factors and potential conservation techniques - Yinying Yang; Yuzheng Wu; Hexuan Long; Xuelin Ma; Kaavian Shariati; James Webb; Liang Guo; Yang Pan; Minglin Ma; Chao Deng; Peng Cao; Jing Chen (Food Security, 2023)

Global honeybee health decline factors and potential conservation techniques - Yinying Yang; Yuzheng Wu; Hexuan Long; Xuelin Ma; Kaavian Shariati; James Webb; Liang Guo; Yang Pan; Minglin Ma; Chao Deng; Peng Cao; Jing Chen (Food Security, 2023)

Spatial distribution, pollution characteristics, and health risks of antibiotic resistance genes in China: a review - Zhixiang Xu; Yue Jia; Bin Huang; Dimeng Zhao; Xin Long; Siyuan Hu; Caiqing Li; Guohua Dao; Bo Chen; Xuejun Pan (Environmental Chemistry Letters, 2023)

A 3D solar-driven evaporator based on electrospun recycled PET film for efficient seawater desalination - Shufang Zhu; Xiaoyu Jia; Yanpeng Ni; Bing Pan; Yunze Long; Dagang Miao; Xu Yan (Journal of Cleaner Production, 2023)

Allergenicity of wheat protein in diet: Mechanisms, modifications and challenges - Ming Liu; Jihong Huang; Sen Ma; Guanghai Yu; Aimei Liao; Long Pan; Yinchen Hou (Food Research International, 2023)

Competitive adsorption of binary negatively charged proteins in egg white during foam evolution: From bulk solution to air-water interface - Haobo Jin; Jiajing Pan; Qi Zeng; Zuyue Li; Yongguo Jin; Long Sheng (Food Hydrocolloids, 2023)

Swc4 protects nucleosome-free rDNA, tDNA and telomere loci to inhibit genome instability - Yue Pan; Can Hu; Lin-Jun Hou; Yu-Long Chen; Jiantao Shi; Jia-Cheng Liu; Jin-Qiu Zhou (DNA Repair, 2023)

Study of the numerical model and humidification strategy of wet-membrane humidifier - Yu Guo; Yukun Wang; Shunzhi Pan; Zhengwei Long; Xiong Shen (Building and Environment, 2023)

Dual improvement in acid and redox properties of the FeO /OAC catalyst via APS oxygen-functionalization: High low-temperature NH3-SCR activity, SO2 and H2O tolerance - Simi Li; Yan Huang; Hong Zhu; Jiaqi Long; Ling Xiao; Pan Li; Lingkui Zhao; Junfeng Zhang (Fuel, 2023)

Oxidative stress mediates the associations between phthalate exposures and thyroid cancer/benign nodule risk - Chong Liu; Long-Qiang Wang; Min Zhang; Yan-Ling Deng; Qiong Luo; Er-Nan Liu; Pan-Pan Chen; Yu Miao; Pan Yang; Qiang Zeng (Environmental Pollution, 2023)

Photooxidation potential of fine particles from desulfurization flue gas aerosol - Xue Gao; Jixin Su; Qi Pan; Xiaoqing Cao; Shan Wu; Xiaoxing Long; Min Song; Yan Wu (Chemical Engineering Journal, 2023)

Flexible SiC nanowire/mullite fiber composite aerogel with adjustable strength based on micromechanical design - Mingyuan Yan; Xudong Cheng; Lunlun Gong; Zhiyi Lun; Pan He; Long Shi; Chenjie Liu; Yuelei Pan (Chemical Engineering Journal, 2023)

5-epi-ent-Kaurane diterpenoids from the aerial parts of Isodon eriocalyx and their anti-atherosclerotic potential - Long Mu; Tian Li; Peng-Lin Wu; Ling-Qiao Cai; Shu-Ying Li; Zi-Yuan Wang; Yuan-Yuan Liu; Jie Wang; Dong Yan; Zheng-Yun Rao; Chao-Jun Wang; Jian Zhang; et al. (Phytochemistry, 2023)

Coupling effect of fiber reinforcement and MICP stabilization on the tensile behavior of calcareous sand - Dian-Long Wang; Chao-Sheng Tang; Xiao-Hua Pan; Bo Liu; Bin Shi (Engineering Geology, 2023)

Novel activation of sulfite by perovskite CaCu3Ti4O12 for As(III) oxidation: Kinetics and mechanism - Qing Shao; Haike Yang; Yingxi Luo; Pan Yang; Liying Long; Yiqun Chen; Zizheng Liu; Feng Wu; Pengchao Xie; Jun Ma (Chemical Engineering Journal, 2023)

A safe anode-free lithium metal pouch cell enabled by integrating stable quasi-solid electrolytes with oxygen-free cathodes - Chuan Zhao; Yu Pan; Runjing Li; Anjun Hu; Bo Zhou; Miao He; Jiahao Chen; Zhongfu Yan; Yining Fan; Nian Chen; Mengjiao Liu; Jianping Long (Chemical Engineering Journal, 2023)

Rational design of molecular phototheranostic platform for NIR-II fluorescence imaging guided chemodynamic-photothermal combined therapy - Gui-long Wu; Bin Sun; Yuxuan He; Xiaofeng Tan; Qi Pan; Sha Yang; Na Li; Minghui Wang; Peixian Wu; Fen Liu; Hao Xiao; Li Tang; et al. (Chemical Engineering Journal, 2023)

A genome-wide co-expression network analysis revealed ZmNRAMP6-mediated regulatory pathway involved in maize tolerance to lead stress - Peng Liu; Li Jiang; Ping Long; Qinglin Li; Fengxia Hou; Guangsheng Yuan; Zhong Chen; Minyan Zhang; Chaoying Zou; Guangtang Pan; Langlang Ma; Yaou Shen (Theoretical and Applied Genetics, 2023)

Cross-sectional rainfall observation on the central-western Tibetan Plateau in the warm season: System design and preliminary results - Kun Yang; Yingying Chen; Lazhu; Changhui Zhan; Xiaoyan Ling; Xu Zhou; Yaozhi Jiang; Xiangnan Yao; Hui Lu; Xiaogang Ma; Lin Ouyang; Weihao Pan; et al. (Science China Earth Sciences, 2023)

Effects of PM2.5 pollution and single nucleotide polymorphisms of neurotrophin signaling pathway genes acting together on schizophrenia relapse - Qinggui Lei; Xiaolan Huang; Tongshun Li; Qingqing Zhong; Qiang Chen; Runde Pan; Jianxiong Long; Li Su (International Archives of Occupational and Environmental Health, 2023)

Rayleigh surface wave inversion based on an improved Archimedes optimization algorithm - Zhen-An Yao; Ren Wang; Fu Yu; Long-Feng Chen; Hong-Xing Li; Xiang-Teng Wang; Pan Wang (Applied Geophysics, 2023)

Heavy metals accumulation in bivalve mollusks collected from coastal areas of southeast China - Xiao-Dong Pan; Jian-Long Han (Marine Pollution Bulletin, 2023)

Evaluation of coal screening performance by spatial image reconstruction method - Jiawang Lu; Chenlong Duan; Miao Pan; Haishen Jiang; Long Huang; Peng Guo; Enkhbat Dombon (Fuel, 2023)

Association between maternal exposure to per- and polyfluoroalkyl substances and serum markers of liver function during pregnancy in China: A mixture-based approach - Qian Liao; Peng Tang; Haoran Fan; Yanye Song; Jun Liang; Huishen Huang; Dongxiang Pan; Meile Mo; LeiLei; Mengrui Lin; Jiehua Chen; Huanni Wei; et al. (Environmental Pollution, 2023)

Experimental investigation of convective heat transfer in the aircraft cabin environment at low air pressure - Xiaojing Zeng; Xin Su; Xuhan Zhang; Wuxuan Pan; Zhengwei Long; Xiong Shen (Building and Environment, 2023)

Preliminary Investigation on Marine Radar Oil Spill Monitoring Method Using YOLO Model - Bo Li; Jin Xu; Xinxiang Pan; Rong Chen; Long Ma; Jianchuan Yin; Zhiqiang Liao; Lilin Chu; Zhiqiang Zhao; Jingjing Lian; Haixia Wang (Journal of Marine Science and Engineering, 2023)
Due to the recent rapid growth of ocean oil development and transportation, the offshore oil spill risk accident probability has increased unevenly. The marine oil spill poses a great threat to the development of coastal cities. Therefore, effective and reliable technologies must be used to monitor oil spills to minimize disaster losses. Based on YOLO deep learning network, an automatic oil spill detection method was proposed. The experimental data preprocessing operations include noise reduction, gray adjustment, and local contrast enhancement. Then, real and synthetically generated marine radar oil spill images were used to make slice samples for training the model in the YOLOv5 network. The detection model can identify the effective oil spill monitoring region. Finally, an adaptive threshold was applied to extract the oil slicks in the effective oil spill monitoring regions. The YOLOv5 detection model generated had the advantage of high efficiency compared with existing methods. The offshore oil spill detection method proposed can support real-time and effective data for routine patrol inspection and accident emergency response.

Anti-neuroinflammatory sesquiterpenoids from Chloranthus henryi - Xue-Jiao Wang; Jun-Li Xin; Sheng-Zhou Yu; Li-Long Pan; Jin-Feng Hu; Juan Xiong (Natural Product Research, 2023)

Deployment optimization of battery swapping stations accounting for taxis’ dynamic energy demand - Tian-yu Zhang; En-jian Yao; Yang Yang; Long Pan; Cui-ping Li; Bin Li; Feng Zhao (Transportation Research Part D: Transport and Environment, 2023)

A quantum algorithm for heat conduction with symmetrization - Shi-Jie Wei; Chao Wei; Peng Lv; Changpeng Shao; Pan Gao; Zengrong Zhou; Keren Li; Tao Xin; Gui-Lu Long (Science Bulletin, 2023)

Comparative proteomic analysis reveals the different hepatotoxic mechanisms of human hepatocytes exposed to silver nanoparticles - Tin Yan Wong; Neng Yan; Kenneth Kin Leung Kwan; Yanrong Pan; Jingjing Liu; Yao Xiao; Long Wu; Henry Lam (Journal of Hazardous Materials, 2023)

Relationships between livestock density and soil phosphorus contents – County and farm level analyses - Meixiu Tan; Yong Hou; Tao Zhang; Yifei Ma; Weitong Long; Chaonan Gao; Pan Liu; Qunchao Fang; Guichao Dai; Shengli Shi; Arjan Reijneveld; Oene Oenema (CATENA, 2023)

A 40 % paddy surface soil organic carbon increase after 5-year no-tillage is linked with shifts in soil bacterial composition and functions - Jian-Ying Qi; Xiang-Bin Yao; Jian Lu; Long-Xin He; Jun-Li Cao; Zheng-Rong Kan; Xing Wang; Sheng-Gang Pan; Xiang-Ru Tang (Science of The Total Environment, 2023)

Rational synthesis of bimetallic CoFe-MOF-74 grown on Ni foam converted into bamboo-shoot-like α-Co(OH)2/CoFe2O4 nanorods for high-performance supercapacitors - Tao-Long Wu; Xiu-Niang Tan; Tian-Tian Nong; Yu-Jie Pan; Peng-Fei Qiu; Jia-Qi He; Yan Zhou; Xue-Cai Tan; Zai-Yin Huang; Lei Han (Chemical Engineering Journal, 2023)

Selective separation of volatile fatty acids, nitrogen and phosphorus from anaerobic acidogenic fermentation via forward osmosis membrane process - Xian-Zheng Zhu; Long-Fei Wang; Xin-Rong Pan; Feng Zhang; Min-Sheng Huang; Wen-Wei Li; Hou-Qi Liu (Chemical Engineering Journal, 2023)

Unveiling the enhancement essence on Li2S deposition by the polarized topological β-polyvinylidene fluoride: Beyond built-in electric field effect - Guo Wen Sun; Meng Jing Jin; Qian Yu Liu; Chao Yue Zhang; Jiang Long Pan; Yan Chun Wang; Xiu Ping Gao; Geng Zhi Sun; Xiao Jun Pan; Jin Yuan Zhou (Chemical Engineering Journal, 2023)

Glycosylated triptolide affords a potent in vivo therapeutic activity to hepatocellular carcinoma in mouse model - Jian Xue; Feng Pan; Tengcong Long; Frank Shujie Hou (Medicinal Chemistry Research, 2023)

A new isolate of Streptomyces lateritius (Z1‐26) with antibacterial activity against fish pathogens and immune enhancement effects on crucian carp ( Carassius auratus ) - Yahui Yang; Duo Jin; Wensu Long; Ximiao Lai; Yunjun Sun; Feng Zhai; Pan Wang; Xixun Zhou; Yibo Hu; Liqiu Xia; Ganfeng Yi (Journal of Fish Diseases, 2023)
The Streptomyces lateritius Z1‐26 was isolated from soil samples which showed broad‐spectrum antibacterial activity against a broad range of fish pathogens. The In Vivo Imaging System (IVIS) monitored that strain Z1‐26 could survive and colonize in the gills and abdomen of crucian carp. The effects of dietary supplementation with strain Z1‐26 were evaluated with respect to the growth performance, antioxidant capacity, and immune response of crucian carp. The results showed that the Z1‐26‐fed fish had a significantly higher growth rate than the fish fed the control diet. The immune and antioxidant parameters revealed that the non‐specific immune indicators (AKP, SOD, and LZM) of the serum, the expression of immune‐related genes ( IgM , C3 , and LZM ), and antioxidant‐related genes ( Nrf2 and Keap1 ) of the immune organs were significantly increased, whereas the expression of pro‐inflammatory factors ( IL‐1β , IL‐8 , and TNF‐α ) of the immune organs was significantly down‐regulated in crucian carp fed strain Z1‐26 compared with fish fed a control diet. Moreover, fish fed with Z1‐26 supplemented diets showed a significantly improved survival rate after Aeromonas hydrophila infection. In addition, the whole genome analysis showed that strain Z1‐26 possesses 28 gene clusters, including 6 polyketide synthetase (PKS), 4 non‐ribosomal peptide‐synthetase (NRPS), 1 bacteriocin, and 1 lantipeptide. In summary, these results indicated that strain Z1‐26 could improve the growth performance and disease resistance in crucian carp, and has the potential to be developed as a candidate probiotics for the control of bacterial diseases in aquaculture.

Production of hydrocarbon-rich bio-oil from catalytic pyrolysis of waste cooking oil over nickel monoxide loaded corn cob-derived activated carbon - Peng Li; Bo Niu; Helin Pan; Yayun Zhang; Donghui Long (Journal of Cleaner Production, 2023)

Enhanced desalination and water transport performance of polyelectrolyte-modified ‘holey’ graphene oxide film - Feng Liu; Qingwen Long; Guiquan Che; Zhihao Zhang; Mick Cooper; Jing Zhang; Gang Pan; Wentao Jiao (Journal of Cleaner Production, 2023)

Leather wastes into high-value chemicals: Keratin-based retanning agents via UV-initiated polymerization - Fei Pan; Yuanhang Xiao; Long Zhang; Jiajing Zhou; Chunhua Wang; Wei Lin (Journal of Cleaner Production, 2023)

Online evaluation of catalytic co-pyrolysis of hemicellulose and polypropylene over CaO catalyst - Junjie Weng; Zhanjun Cheng; Yi Zhang; Chao Jiang; Lin Long; Jian Wang; Jianfeng Pan (Fuel, 2023)

Discrimination of the harvesting season of green tea by alcohol/salt-based aqueous two-phase systems combined with chemometric analysis - Xiao-Hua Zhang; Hui-Na Cui; Jing-Jing Zheng; Xiang-Dong Qing; Kai-Long Yang; Ya-Qian Zhang; Lu-Meng Ren; Le-Yuan Pan; Xiao-Li Yin (Food Research International, 2023)

Comprehensive identification and hydrophobic analysis of key proteins affecting foam capacity and stability during the evolution of egg white foam - Haobo Jin; Yongguo Jin; Jiajing Pan; Sijie Mi; Qi Zeng; Zhe Li; Qi Wang; Yi Sun; Long Sheng (Food Hydrocolloids, 2023)

Bioinspired SiC aerogels for super thermal insulation and adsorption with super-elasticity over 100,000 times compressions - Mingyuan Yan; Xudong Cheng; Long Shi; Yuelei Pan; Pan He; Zhongxin Zhang; Zhiyi Lun; Yangyang Fu; Heping Zhang (Chemical Engineering Journal, 2023)

Tailoring mixed geometrical configurations in amorphous catalysts to activate oxygen electrode reactions of lithium-oxygen batteries - Runjing Li; Anjun Hu; Chuan Zhao; Bo Zhou; Miao He; Yining Fan; Jiahao Chen; Zhongfu Yan; Yu Pan; Jianping Long (Chemical Engineering Journal, 2023)

Retraction Note: LINC00665/miR-9-5p/ATF1 is a novel axis involved in the progression of colorectal cancer - Xuhong Zhao; Wenhao Weng; Yin Long; Weijie Pan; Zhi Li; Fenyong Sun (Human Cell, 2022)

Associations of bisphenol exposure with thyroid hormones in pregnant women: a prospective birth cohort study in China - Huishen Huang; Jun Liang; Peng Tang; Chuanxiang Yu; Haoran Fan; Qian Liao; Jinghua Long; Dongxiang Pan; Xiaoyun Zeng; Shun Liu; Dongping Huang; Xiaoqiang Qiu (Environmental Science and Pollution Research, 2022)

Occurrence, transport, and toxicity of nanomaterials in soil ecosystems: a review - Zhixiang Xu; Xin Long; Yue Jia; Dimeng Zhao; Xuejun Pan (Environmental Chemistry Letters, 2022)

Association of soft drink and 100% fruit juice consumption with all-cause mortality, cardiovascular diseases mortality, and cancer mortality: A systematic review and dose-response meta-analysis of prospective cohort studies - Bei Pan; Long Ge; Honghao Lai; Qi Wang; Qi Wang; Qian Zhang; Min Yin; Sheng Li; Jinhui Tian; Kehu Yang; Jiancheng Wang (Critical Reviews in Food Science and Nutrition, 2022)

Damage and Failure Characteristics and Constitutive Model of Copper-Bearing Skarns Disturbed by Hierarchical Dynamic Loading After Loading And Unloading - Chun Wang; Jia Li; Lu- ping Cheng; Xin-ru Li; Pan-long Zhang; Man-gu Hu (Rock Mechanics and Rock Engineering, 2022)

A novel bio-washing eluent obtained from fermentation of fruit wastes for removal of soil Pb: efficiency, mechanism, and risk assessment - Xiaomei Pan; Shirong Zhang; Ting Li; Guiyin Wang; Xiaoxun Xu; Yun Li; Wei Zhou; Jinsong He; Lulu Long; Ouping Deng; Ling Luo; Guoshu Gong (Environmental Science and Pollution Research, 2022)

Semi-solid anaerobic co-digestion of source-separated fecal slag and food waste: focusing on methane production, ecological risk assessment, and quality evaluation as fertilizer - Hamza Hassan Yusuf; Xiaofang Pan; Guanjing Cai; Jiasheng Cai; Xuewei Huang; Zhi-Long Ye (Environmental Science and Pollution Research, 2022)

Characterization of Fine-Scale Turbulence Generated in a Laboratory Orbital Shaker and Its Influence on Skeletonema costatum - Lin Yu; Yifan Li; Zhongzhi Yao; Long You; Zong-Pei Jiang; Wei Fan; Yiwen Pan (Journal of Marine Science and Engineering, 2022)
Turbulence is one of the ubiquitous aspects of aquatic systems and affects many physical and biological processes. Based on direct velocity measurements and a computational fluid dynamics (CFD) simulation, we characterized the distribution of the turbulent kinetic dissipations rates (ε) in an orbital shaker system within a range of rotation frequencies. CFD was able to estimate the ε distribution in containers accurately, which was confirmed by other two methods and was independent of velocity measurement. The results showed that ε was linearly correlated with the rotational frequencies. Despite the existence of gradients of ε and the fact that a mean circular horizontal flow was formed within the tank, the energy levels of the whole tank varied spatially within an order of magnitude and the ε distributions at different rotational frequencies were similar, suggesting that the ε distribution in the whole tank could be seen as quasi-homogeneous. To investigate the influence of turbulence on algae growth, culture experiments of a typical diatom—Skeletonema costatum were carried out under different turbulence conditions. Our results suggested turbulence mixing promoted nutrient uptake and growth of Skeletonema costatum, which could be attributed to the break of the diffusion-limited resource concentration boundary layer surrounding phytoplankton.

Ultrasound-targeted microbubble destruction (UTMD)-mediated miR-150-5p attenuates oxygen and glucose deprivation-induced cardiomyocyte injury by inhibiting TTC5 expression - Xin Zhong; Yu Chen; Xiangdang Long; Hongtian Chen; Zhaofen Zheng; Hongwei Pan; Jianqiang Peng; Yanfu Liu; Haijun Wang; Yongjun Hu (Molecular Biology Reports, 2022)

Amelioration of Flesh Quality in Hybrid Grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatu) Fed With Oxidized Fish Oil Diet by Supplying Lactobacillus pentosus - Xiaobo Yan; Simiao Pan; Zhihao Li; Xiaohui Dong; Beiping Tan; Shuisheng Long; Tao Li; Xiangxiang Suo; Yuanzhi Yang (Frontiers in Marine Science, 2022)
The objective was to investigate the improvement of the flesh quality and nutritional value of hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatu ) by Lactobacillus pentosus (BL-15). The two diets were prepared with 9% oxidized fish oil (OFO negative control group) or 9% fresh fish oil (FFO positive control group) as the major lipid source, and the OFO diet were sprayed with L. pentosus at 1.0×10 7 , 1.0×10 8 , 1.0×10 9 CFU/g, respectively. Five kinds of diets were fed to hybrid grouper with initial weight of 21.36 ± 0.03 g for 60 days. The results showed that (1) consumption of OFO diet significantly increased muscle crude lipid, total cholesterol, and total monounsaturated fatty acids contents and significantly decreased muscle C20:5n3, C22:6n3, ∑PUFA levels of grouper ( p < 0.05), whereas the addition of L. pentosus to OFO diet significantly reduced muscle crude lipid, malondialdehyde, reactive oxygen radicals, total cholesterol concentration, increased C20:5n3, C22:6n3, ∑PUFA levels, increased muscle crude protein content, and enhanced muscle hardness, gumminess, and chewiness compared with FFO or OFO group ( p < 0.05). (2) In addition, ingestion of OFO diet significantly increased muscle phenylalanine content and significantly decreased aspartic acid content ( p < 0.05), while the addition of L. pentosus restored aspartic acid to the level not significantly different from that of FFO group ( p > 0.05). The addition of L. pentosus also increased tyrosine, lysine, leucine, phenylalanine, arginine, and alanine content compared to FFO group at the same time ( p < 0.05). (3) Furthermore, the intake of OFO diet would lead to deterioration in muscle flavor quality and increase in noxious odors in grouper, and the addition of L. pentosus can mitigate or rectify these detrimental consequences. In further analysis, consumption of OFO group significantly downregulated the mRNA expression of muscle growth factors and caused serious damage to the muscle antioxidant system ( p < 0.05), which was protected against by the potent antioxidant properties of L. pentosus . We recommend the supplementation level of L. pentosus to be 1.0×10 9 CFU/g under the highly oxidized conditions of the present trial fish oil.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Effects of three feeding modes on the metabolism, antioxidant capacity, and metabolome of the adult male Chinese mitten crab Eriocheir sinensis - Xiaowen Long; Jie Pan; Nicholas M. Wade; Yunfei Sun; Yuming Liu; Yongxu Cheng; Xugan Wu (Aquaculture International, 2022)

The Effects of Ground and Treadmill Running on Energy Metabolism and Muscle Contractile Properties: A Randomized Cross-Over Study - Yuan Zhou; Jian-gang Chen; Xiao-long Li; Xin-liang Pan; Yi-zheng Zhou; Zheng-ao Li; Zhi-cheng Liang; Jia-min Long; Ming-ze Qin; Jing Zhang; Bing Shi; Bing-jun Wan; et al. (Journal of Science in Sport and Exercise, 2022)
Purpose This study aimed to compare the effects of ground and treadmill running on energy metabolism and muscle contractile properties, providing a basis for the general public to choose running venues. Methods Ten male college students (age, 20.10 ± 1.53 years; height, 176.20 ± 5.49 cm; weight, 72.14 ± 8.25 kg; body fat percent, 12.41% ± 4.65%) were recruited in this study. Energy expenditure (EE) was measured using the accelerometer (GT9X) combined with specific estimation equations. Average heart rate (HR) was measured using a heart rate band (Polar). Muscle contractile properties were assessed by measuring muscle displacement (Dm) and contraction velocity (Vc) using tensiomyography (TMG-S1). Blood glucose (Glu) and lactate (Lac) were measured by portable devices (eB-G and Lactate Scout). The running speed was 9 km/h and the duration was 25 min. Two-way ANOVA (protocol × time) was used to analyze the effect of running protocols on energy metabolism and muscle contractile properties. Results EE of treadmill running was significantly higher than EE of ground running (protocol main effect, P < 0.001), and HR of treadmill running was significantly higher than that of ground running in the first testing time (protocol simple effect, P = 0.026; protocol × time interaction P = 0.043). The decrease in Dm of the rectus femoris after treadmill running was significantly higher than that of ground running (protocol main effect, P = 0.009). The interaction of different running protocols and testing times on Lac was significant ( P = 0.025), but all results of the simple effects analysis were not statistically significant ( P > 0.05). Conclusion Our study found a difference in energy expenditure between treadmill and ground running at 9 km/h with duration of 25 min. In addition, treadmills are more likely to cause a decrease in muscle displacement distance of the rectus femoris measured after exercise than ground running. Future studies are needed to further investigate whether the differences are induced by internal metabolism or the environmental conditions of running.

Magnetic properties of surface sediments from Liuxi River, southern China and their environmental significance - Erqi Zheng; Yang Bai; Mingkun Li; Tingping Ouyang; Fangzhi Zhang; Mingjie Yu; Gang Lei; Zhiyi Pan; Gang Long (Journal of Soils and Sediments, 2022)

Three new 3-formyl-2-arylbenzofurans from Itea yunnanensis and their anti-hepatocellular carcinoma effects - Tian-Qiong Lang; Guo-Yong Luo; Wen-Chen Pu; Zhi-Wei Wang; Jian Wang; Xiao-Long Tian; Pan Zhang; Neng-Wu Zhao; Wu-De Yang; Hui-Fang Chai (Natural Product Research, 2022)

Dynamic response of the heterogeneous deep-sea sediment with nonlinear gradient modulus to mining machine loading - Wei Zhu; Jinxin Pan; Wenbo Ma; Shan Deng; Wujun Zhou; Wenyao Liu; Shiguo Long; Caiqian Yang; Lingyun You (Marine Georesources & Geotechnology, 2022)

Avilamycin production enhancement by mutagenesis and fermentation optimization in Streptomyces viridochromogenes - Guanghai Yu; Haifen Peng; Jian Cao; Aimei Liao; Pan Long; Jihong Huang; Ming Hui (World Journal of Microbiology and Biotechnology, 2022)

MouseVenue3D: A Markerless Three-Dimension Behavioral Tracking System for Matching Two-Photon Brain Imaging in Free-Moving Mice - Yaning Han; Kang Huang; Ke Chen; Hongli Pan; Furong Ju; Yueyue Long; Gao Gao; Runlong Wu; Aimin Wang; Liping Wang; Pengfei Wei (Neuroscience Bulletin, 2022)

Effect of tree form on wheat yield via changing microenvironment in almond–wheat intercropping - Wen Zhang; Hui Xie; Shou-An Han; Min Wang; Ming-Qi Pan; Xu Qiao; Long Li (Agroforestry Systems, 2022)

Fatty acid-binding protein 5 activates cyclooxygenase-2 and promotes hypoxic injury in LO2 cells - Long Pan; Yihan Pang; Heng Xiao; Xin Deng; Qingsong Chen (Molecular & Cellular Toxicology, 2022)

Clinical and Molecular Features of POLG-Related Sensory Ataxic Neuropathy with Dysarthria and Ophthalmoparesis - Li-Xi Li; Li-Ting Jiang; You-Gui Pan; Xiao-Long Zhang; Li-Zhen Pan; Zhi-Yu Nie; Yu-Hui Chen; Ling-Jing Jin (Journal of Molecular Neuroscience, 2021)

The Effect of Oxidized Fish Oil on the Spleen Index, Antioxidant Activity, Histology and Transcriptome in Juvenile Hybrid Grouper (♀ Epinephelus fuscoguttatus × ♂ Epinephelus lanceolatus) - Shuisheng Long; Zhihao Li; Xiaohui Dong; Xiaobo Yan; Hao Liu; Beiping Tan; Shuang Zhang; Simiao Pan; Tao Li; Xiangxiang Suo; Yuanzhi Yang (Frontiers in Marine Science, 2021)
The spleen is an important organ in the immune function of fish, and it is also important for hematogenesis and antibody and granulocyte production. However, the effect of oxidized fish oil on the spleen of hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ Epinephelus lanceolatus ) is unknown. In this study, hybrid groupers were fed with oxidized fish oil and the spleen index, antioxidant ability, histology and transcriptome were investigated. Oxidized fish oil did not affect the spleen index. Levels of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px) and malondialdehyde (MDA) in the spleen were significantly increased as the amount of oxidized fish oil in the diet increased, but the vitamin E concentration was significantly decreased. The morphological organization of the spleen was damaged with increased oxidative stress. And the spleen reacted to oxidative stress by platelet activation, FOXO and notch signaling pathways, which involved amyloid beta precursor protein binding family B member 1 interacting protein (APBB1IP) gene, glucose-6-phosphatase (G6PC) gene, histone acetyltransferase p300 (EP300) gene, insulin gene and notch 2 gene. In conclusion, the oxidized fish oil caused oxidative stress and damaged its structure. Additionally, oxidized fish oil changed the transcription profile of the spleen.

Genomic analysis of a pure culture of magnetotactic bacterium Terasakiella sp. SH-1 - Haijian Du; Wenyan Zhang; Wei Lin; Hongmiao Pan; Tian Xiao; Long-Fei Wu (Journal of Oceanology and Limnology, 2021)

Observations on a magnetotactic bacteria-grazing ciliate in sediment from the intertidal zone of Huiquan Bay, China - Si Chen; Kaixuan Cui; Wenyan Zhang; Yicong Zhao; Tian Xiao; Hongmiao Pan; Wuchang Zhang; Long-Fei Wu (Journal of Oceanology and Limnology, 2021)

How light affect the magnetotactic behavior and reproduction of ellipsoidal multicellular magnetoglobules? - Xinxin Qian; Yicong Zhao; Claire-Lise Santini; Hongmiao Pan; Tian Xiao; Haitao Chen; Tao Song; Jinhua Li; Francois Alberto; Sophie Brustlein; Long-Fei Wu (Journal of Oceanology and Limnology, 2021)

Characterization and diversity of magnetotactic bacteria from sediments of Caroline Seamount in the Western Pacific Ocean - Kaixuan Cui; Wenyan Zhang; Jia Liu; Cong Xu; Yicong Zhao; Si Chen; Hongmiao Pan; Tian Xiao; Long-Fei Wu (Journal of Oceanology and Limnology, 2021)

Efficiency and comprehensive risk assessment of soil Pb and Cd by washing technique with three biodegradable eluents - Qinmei Zhong; Shirong Zhang; Xiaomei Pan; Guiyin Wang; Xiaoxun Xu; Ting Li; Wei Zhou; Yan He; Ling Luo; Yan Liu; Lulu Long (Environmental Science and Pollution Research, 2021)

Low-cost sensor outlier detection framework for on-line monitoring of particle pollutants in multiple scenarios - Yinyue Xu; Zhengwei Long; Wuxuan Pan; Yukun Wang (Environmental Science and Pollution Research, 2021)

OSI-027 alleviates rapamycin insensitivity by modulation of mTORC2/AKT/TGF-β1 and mTORC1/4E-BP1 signaling in hyperoxia-induced lung injury infant rats - Li Long; Mulin Liang; Yanling Liu; Pan Wang; Hongxing Dang (Molecular & Cellular Toxicology, 2021)

Creep characteristics and constitutive model for frozen mixed soils - Bing-tang Song; En-long Liu; Zhao-yun Shi; Pan Wang; Qi-hao Yu (Journal of Mountain Science, 2021)

Immunity improvement and gut microbiota remodeling of mice by wheat germ globulin - Guanghai Yu; Xiaoguo Ji; Jihong Huang; Aimei Liao; Long Pan; Yinchen Hou; Ming Hui; Weiyun Guo (World Journal of Microbiology and Biotechnology, 2021)

Subcellular Localization of the D27 Protein in Sugarcane (Saccharum spp. Hybrids) Using an Optimized Protoplast Isolation, Purification, and Transient Gene Expression Protocol - Zhuan-di Wu; Xin Hu; Feng-gang Zan; Yong-bao Pan; David M. Burner; Zheng-ying Luo; Jia-yong Liu; Li-ping Zhao; Li Yao; Yong Zhao; Xin-long Liu; Hong-ming Xia; et al. (Sugar Tech, 2021)

Global patterns in leaf stoichiometry across coastal wetlands - Yu‐Kun Hu; Xu‐Yan Liu; Nian‐Peng He; Xu Pan; Song‐Yuan Long; Wei Li; Man‐Yin Zhang; Li‐Juan Cui (Global Ecology and Biogeography, 2021)
Aim Coastal wetlands provide crucial ecosystem functions and services, such as coastal protection, nutrient retention and C sequestration. Despite the important roles in global C, N and P cycling, the global variation in leaf stoichiometry across coastal wetlands remains unclear. Location Global. Time period 1980–2018. Major taxa studied Vascular plants. Methods By compiling a global dataset of 698 data records in 205 sites, we carried out systematic analyses of the world‐wide trends and their determinants of leaf element contents and ratios of plants across coastal wetlands. Results Leaf N and P contents increased significantly, but C:N, C:P and N:P ratios decreased with increasing latitude in coastal wetlands. The mean annual temperature was the predominant driver of leaf N, P and C:N, whereas soil N:P was a good predictor of leaf C:P and N:P ratios. Furthermore, N increased faster with P in plant leaves of coastal wetlands compared with terrestrial ecosystems. Within coastal wetlands, herb‐dominated salt marshes had a significantly higher leaf P content, lower leaf N:P ratio and lower scaling exponent of leaf N to P than tree‐dominated mangroves. Main conclusions The similar latitudinal patterns of leaf stoichiometry in coastal wetlands compared with terrestrial ecosystems reflected the similar influences of temperature. However, different slopes of leaf P and N:P ratios and N and P scaling relationships between these two ecosystems suggested that different salinity and tidal inundation levels result in different strategies of N and P use in coastal wetland plants. These differences in leaf stoichiometry between ecosystems and between different types of coastal wetlands might need to be emphasized in future biogeochemical modelling owing to their different roles in global nutrient and carbon cycling.

Chemical constituents from Jasminum pentaneurum Hand.-Mazz and their cytotoxicity against human cancer cell lines - Wei Wei; Er-Wei Hao; Meng Zhang; Xiang-Long Pan; Jian-Feng Qin; Jin-Ling Xie; Jiang-Yu Zhou; Xiao-Tao Hou; Jia-Gang Deng (Natural Product Research, 2021)

Low-cost sensor system for monitoring the oil mist concentration in a workshop - Hongsheng Zhang; Siyi Zhang; Wuxuan Pan; Zhengwei Long (Environmental Science and Pollution Research, 2021)

LINC00472 regulates vascular smooth muscle cell migration and proliferation via regulating miR-149-3p - Ran Jing; Wei Pan; Tianyi Long; Zhenyu Li; Chuanchang Li (Environmental Science and Pollution Research, 2021)

The insect-killing bacterium Photorhabdus luminescens has the lowest mutation rate among bacteria - Jiao Pan; Emily Williams; Way Sung; Michael Lynch; Hongan Long (Marine Life Science & Technology, 2021)
Mutation is a primary source of genetic variation that is used to power evolution. Many studies, however, have shown that most mutations are deleterious and, as a result, extremely low mutation rates might be beneficial for survival. Using a mutation accumulation experiment, an unbiased method for mutation study, we found an extremely low base-substitution mutation rate of 5.94 × 10 –11 per nucleotide site per cell division (95% Poisson confidence intervals: 4.65 × 10 –11 , 7.48 × 10 –11 ) and indel mutation rate of 8.25 × 10 –12 per site per cell division (95% confidence intervals: 3.96 × 10 –12 , 1.52 × 10 –11 ) in the bacterium Photorhabdus luminescens ATCC29999. The mutations are strongly A/T-biased with a mutation bias of 10.28 in the A/T direction. It has been hypothesized that the ability for selection to lower mutation rates is inversely proportional to the effective population size (drift-barrier hypothesis) and we found that the effective population size of this bacterium is significantly greater than most other bacteria. This finding further decreases the lower-bounds of bacterial mutation rates and provides evidence that extreme levels of replication fidelity can evolve within organisms that maintain large effective population sizes.

Prevalence and outcomes of re-positive nucleic acid tests in discharged COVID-19 patients - Hou-wei Du; Jun-nian Chen; Xiao-bin Pan; Xiao-ling Chen; Yixian-Zhang; Shuang-fang Fang; Xiao-qing Li; Pin-cang Xia; Lei Gao; Hai-long Lin; Li-min Chen; Nan Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Economic policy choice of governing haze pollution: evidence from global 74 countries - Feng Dong; Xiaojie Zhang; Yajie Liu; Yuling Pan; Xiaoyun Zhang; Ruyin Long; Ziyuan Sun (Environmental Science and Pollution Research, 2021)

Effects of straw decayed products of four crops on the amelioration of soil acidity and maize growth in two acidic Ultisols - Xiao-ying Pan; Ren-kou Xu; Jackson Nkoh Nkoh; Hai-long Lu; Hui Hua; Peng Guan (Environmental Science and Pollution Research, 2021)

Comparative proteomic analysis of parasitic loranthus seeds exposed to dehydration stress - Limei Pan; Lingyun Wan; Lili He; Lisha Song; Hairong Long; Xiaowen Ji; Ni Jiang; Juan Huo; Shugen Wei; Jine Fu (Plant Biotechnology Reports, 2021)

NC10 bacteria promoted methane oxidation coupled to chlorate reduction - Zi-Yan Li; Xin Li; Bin Tan; Pan-Long Lv; He-Ping Zhao (Biodegradation, 2020)

Polymorphisms of the growth hormone gene and their association with growth traits and sex in Sarcocheilichthys sinensis - Chuankun Zhu; Zhengjun Pan; Guoliang Chang; Hui Wang; Huaiyu Ding; Nan Wu; Xiaogang Qiang; Xiangsheng Yu; Long Wang; Ji Zhang (Molecular Genetics and Genomics, 2020)

Effects of freezing-thawing on the engineering performance of core wall soil materials of a dam in the process of construction - Xiu-ling Ren; Qi-hao Yu; Gui-ke Zhang; Pan Yue; En-long Liu; Zhen-yu Zhang; Yan-hui You (Journal of Mountain Science, 2020)

Facile preparation of L-cysteine–modified cellulose microspheres as a low-cost adsorbent for selective and efficient adsorption of Au(III) from the aqueous solution - Xin Yang; Qi Pan; Yinyong Ao; Jifu Du; Zhen Dong; Maolin Zhai; Long Zhao (Environmental Science and Pollution Research, 2020)

Cellulose-based adsorbents loaded with zero-valent iron for removal of metal ions from contaminated water - Xiaoning Li; Jinyao Zhang; Hongtian Xie; Yuanfeng Pan; Jie Liu; Zhihong Huang; Xiang Long; Huining Xiao (Environmental Science and Pollution Research, 2020)

Assessment of Fresh and Dry Rice Straw for Biogas Potential by Anaerobic Digestion - Qiangqiang Liu; Shiyou Pan; Zhongmin Long; Zhenchong Li; Liqin Du; Yutuo Wei (BioEnergy Research, 2020)

RETRACTED ARTICLE: LINC00665/miR-9-5p/ATF1 is a novel axis involved in the progression of colorectal cancer - Xuhong Zhao; Wenhao Weng; Yin Long; Weijie Pan; Zhi Li; Fenyong Sun (Human Cell, 2020)

A Novel Gene Bombyx mori Carotenoid Oxygenases and Retinal Isomerase (BmCORI) Related to β-Carotene Depletion - Xiao-long Dong; Cai-xia Pan; Min-juan Zhang (Biochemical Genetics, 2020)

Establishment of a maize callus regeneration system from haploid shoot tips - Yun Long; Yun Yang; Fei Ge; Guangtang Pan; Yaou Shen (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Phenotypic and Molecular Characterization of a Core Collection of Saccharum spontaneum L. in China - Chao-hua Xu; Xin-long Liu; David M. Burner; Zaheer Abbas; Yong-Bao Pan; Ibrahim Soliman Elgamal; Xin Lu; Huo-sheng Su (Sugar Tech, 2020)

Evaluation of degradation of a novel sulfone bactericide in soils: identification of degradation product and kinetics study - X. G. Meng; X. F. Long; N. Wang; S. Z. Pan; B. A. Song; D. Y. Hu (International Journal of Environmental Science and Technology, 2020)

Cost-reduction strategies in massive genomics experiments - Haichao Li; Kun Wu; Chenchen Ruan; Jiao Pan; Yujin Wang; Hongan Long (Marine Life Science & Technology, 2019)
Many modern biology studies require deep, whole-genome sequencing of hundreds to thousands of samples. Although per-sample costs have dramatically decreased, the total budget for such massive genome sequencing constitutes a significant barrier for poorly funded labs. The costly lab tools required for genomics experiments further hinder such studies. Here, we share two strategies for extensively reducing the costs of massive genomics experiments, including miniaturization of the NEBNext Ultra II FS DNA Library Prep Kit for Illumina (reducing the per-sample total costs to ~ 1/6 of that charged by service providers) and in-lab 3D model-designing of genomics tools. These strategies not only dramatically release funding pressure for labs, but also provide students with additional training in hands-on genomics and 3D-model-designing skills, demonstrating the high potential for their application in genomics experiments and science education.

Rapid adaptation of Brachionus angularis (Rotifera) to invasion by Brachionus calyciflorus - Yi-Long Xi; Ke-Qiang Huang; Ling Pan; Han Zhu; Ya-Li Ge; Xin-Li Wen; Xian-Ling Xiang (Hydrobiologia, 2019)

Distinct biological characterization of the CD44 and CD90 phenotypes of cancer stem cells in gastric cancer cell lines - Xiong Shu; Huiqi Liu; Yunzhi Pan; Lichao Sun; Long Yu; Lixin Sun; Zhihua Yang; Yuliang Ran (Molecular and Cellular Biochemistry, 2019)

Archaeal community structure in sediments from a seamount in the Mariana Volcanic Arc - Wenyan Zhang; Jia Liu; Yi Dong; Xuegang Li; Cong Xu; Tian Xiao; Hongmiao Pan; Long-Fei Wu (Journal of Oceanology and Limnology, 2019)

Potassium Stimulation of IAA Transport Mediated by the Arabidopsis Importer AUX1 Investigated in a Heterologous Yeast System - Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Shih-Ming Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2019)

Mechanism of toppling and deformation in hard rock slope: a case of bank slope of Hydropower Station, Qinghai Province, China - Jun-chao Cai; Neng-pan Ju; Run-qiu Huang; Da Zheng; Wei-hua Zhao; Long-qi Li; Jian Huang (Journal of Mountain Science, 2019)

Shaking table test to assess seismic response differences between steep bedding and toppling rock slopes - Long-qi Li; Neng-pan Ju; Shuai Zhang; Xiao-xue Deng (Bulletin of Engineering Geology and the Environment, 2019)

Correction to: Seismic wave propagation characteristic and its effects on the failure of steep jointed anti-dip rock slope - Long-qi Li; Neng-pan Ju; Shuai Zhang; Xiao-xue Deng; Daichao Sheng (Landslides, 2019)

Seismic wave propagation characteristic and its effects on the failure of steep jointed anti-dip rock slope - Long-qi Li; Neng-pan Ju; Shuai Zhang; Xiao-xue Deng; Daichao Sheng (Landslides, 2019)

Positive PCNA and Ki-67 Expression in the Testis Correlates with Spermatogenesis Dysfunction in Fluoride-Treated Rats - Wen-peng Zhao; Hong-wei Wang; Jing Liu; Pan-pan Tan; Xiang-long Luo; Shi-quan Zhu; Xue-li Chen; Bian-hua Zhou (Biological Trace Element Research, 2018)

Transcriptome analysis to identify the Ras and Rap1 signal pathway genes involved in the response of TM3 Leydig cells exposed to zearalenone - Mingyang Wang; Nan Wang; Jingjing Tong; Jiawen Pan; Miao Long; Peng Li (Environmental Science and Pollution Research, 2018)

The primate extinction crisis in China: immediate challenges and a way forward - Baoguo Li; Ming Li; Jinhua Li; Pengfei Fan; Qingyong Ni; Jiqi Lu; Xuming Zhou; Yongcheng Long; Zhigang Jiang; Peng Zhang; Zhipang Huang; Chenming Huang; et al. (Biodiversity and Conservation, 2018)

Associations of HSP90AA2 gene polymorphisms with disease susceptibility, glucocorticoids efficacy and health-related quality of life in Chinese systemic lupus erythematosus patients - Man Zhang; Su-Su Li; Qiao-Mei Xie; Jian-Hua Xu; Xiu-Xiu Sun; Fa-Ming Pan; Sheng-Qian Xu; Sheng-Xiu Liu; Jin-Hui Tao; Shuang Liu; Jing Cai; Pei-Ling Chen; et al. (Genes & Genomics, 2018)

Physiological and Biochemical Mechanisms Preventing Cd Toxicity in the New Hyperaccumulator Abelmoschus manihot - Mengxi Wu; Qiao Luo; Yin Zhao; Yue Long; Shiliang Liu; Yuanzhi Pan (Journal of Plant Growth Regulation, 2018)

Yak and Tibetan sheep trampling inhibit reproductive and photosynthetic traits of Medicago ruthenica var. inschanica - Hong Xiao; Zhen Peng; Chang Lin Xu; De Gang Zhang; Jin Long Chai; Tao Tao Pan; Xiao Jun Yu (Environmental Monitoring and Assessment, 2018)

Characterization of dominant giant rod-shaped magnetotactic bacteria from a low tide zone of the China Sea - Zhaojie Teng; Wenyan Zhang; Yiran Chen; Hongmiao Pan; Tian Xiao; Long-Fei Wu (Journal of Oceanology and Limnology, 2018)

Regulation of H+-pyrophosphatase by 14-3-3 Proteins from Arabidopsis thaliana - Yu-Di Hsu; Yu-Fen Huang; Yih-Jiuan Pan; Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2018)

Fluorescent Carbon Dots as Cost-Effective and Facile Probes for Caffeic Acid Sensing via a Fluorescence Quenching Process - Qianqian Sun; Yuwei Long; Hongxi Li; Shuang Pan; Jidong Yang; Shaopu Liu; Xiaoli Hu (Journal of Fluorescence, 2018)

The effect of electron competition on chromate reduction using methane as electron donor - Pan-Long Lv; Liang Zhong; Qiu-Yi Dong; Shi-Lei Yang; Wei-Wei Shen; Quan-Song Zhu; Chun-Yu Lai; An-Cheng Luo; Youneng Tang; He-Ping Zhao (Environmental Science and Pollution Research, 2018)

Effect of Electrospun Fibrous Scaffolds with Different Fiber Orientations on the Alignment of Microvessel-Like Structures - Zhenzhen Wu; Tao Yang; Chongyun Bao; Mingzheng Li; Hockin H. K. Xu; XueJuan Liao; Long Li; Ranran Huang; Jian Pan; Xian Liu (Journal of Medical and Biological Engineering, 2018)

BMP7 plays a critical role in TMEM100-inhibited cell proliferation and apoptosis in mouse metanephric mesenchymal cells in vitro - Die Ren; Pan Ju; Jianing Liu; Dongsheng Ni; Yuping Gu; Yaoshui Long; Qin Zhou; Yajun Xie (In Vitro Cellular & Developmental Biology - Animal, 2018)

Controlling mechanism of absence seizures by deep brain stimulus applied on subthalamic nucleus - Bing Hu; Yu Guo; Xiaoqiang Zou; Jing Dong; Long Pan; Min Yu; Zhejia Yang; Chaowei Zhou; Zhang Cheng; Wanyue Tang; Haochen Sun (Cognitive Neurodynamics, 2018)

Lipopolysaccharide aggravated DOI-induced Tourette syndrome: elaboration for recurrence of Tourette syndrome - Long Hongyan; Si Zhenyang; Wang Chunyan; Pan Qingqing (Metabolic Brain Disease, 2017)

Investigation of Perfluoroalkyl Substances (PFASs) in Sediments from the Urban Lakes of Anqing City, Anhui Province, China - Fasong Li; Hanyu Huang; Zhibing Xu; Hui Ni; Hao Yan; Ran Chen; Yan Luo; Wei Pan; Jinyun Long; Xiaofang Ye; Xiaofen Qian; Guangming Yu (Bulletin of Environmental Contamination and Toxicology, 2017)

Efficient and Product-Controlled Depolymerization of Lignin Oriented by Raney Ni Cooperated with Cs x H3 − x PW12O40 - Xiao-Jun Shen; Jia-Long Wen; Pan-Li Huang; Kai Zheng; Shuang-Fei Wang; Qiu-Yun Liu; Adam Charlton; Run-Cang Sun (BioEnergy Research, 2017)

Provenance evolution of the Jurassic northern Qaidam Basin (West China) and its geological implications: evidence from detrital zircon geochronology - Long Yu; Ancheng Xiao; Lei Wu; Yuntao Tian; Martin Rittner; Qianqian Lou; Xiaotian Pan (International Journal of Earth Sciences, 2017)

FLOURY ENDOSPERM8, encoding the UDP-glucose pyrophosphorylase 1, affects the synthesis and structure of starch in rice endosperm - Wuhua Long; Bangning Dong; Yihua Wang; Pengyi Pan; Yunlong Wang; Linglong Liu; Xiaoli Chen; Xi Liu; Shijia Liu; Yunlu Tian; Liangming Chen; Jianmin Wan (Journal of Plant Biology, 2017)

Effectiveness of Fiber Bragg Grating monitoring in the centrifugal model test of soil slope under rainfall conditions - Long-qi Li; Neng-pan Ju; Yong-xing Guo (Journal of Mountain Science, 2017)

Heat shock protein 90 is a stress and immune response gene in the giant spiny frog Quasipaa spinosa - Shu Miao-An; Tu Dan-Dan; Zhang Pan; Long Chen; Gu Wen-Bin; Zhou Zhong-Kai (Fisheries Science, 2017)

Characterization of uncultivated magnetotactic bacteria from the sediments of Yuehu Lake, China - Haijian Du; Rui Zhang; Wenyan Zhang; Cong Xu; Yiran Chen; Hongmiao Pan; Ke Zhou; Long-fei Wu; Tian Xiao (Acta Oceanologica Sinica, 2017)

MicroRNA-146a Promotes Oligodendrogenesis in Stroke - Xian Shuang Liu; Michael Chopp; Wan Long Pan; Xin Li Wang; Bao Yan Fan; Yi Zhang; Haifa Kassis; Rui Lan Zhang; Xiao Ming Zhang; Zheng Gang Zhang (Molecular Neurobiology, 2017)

Magnetically separable maghemite/montmorillonite composite as an efficient heterogeneous Fenton-like catalyst for phenol degradation - Mingjie Jin; Mingce Long; Hanrui Su; Yue Pan; Qiuzhuo Zhang; Juan Wang; Baoxue Zhou; Yanwu Zhang (Environmental Science and Pollution Research, 2017)

Caspase-like proteases regulate aluminum-induced programmed cell death in peanut - Shaochang Yao; Wenjing Huang; Chunliu Pan; Jie Zhan; Long-Fei He (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Long-term treatment of spontaneously hypertensive rats with PD123319 and electrophysiological remodeling of left ventricular myocardium - Xiao Ying; Guan Kai-pan; Long Wei-qing; Peng Long-yun; Wu De-xi; Huang Zhi-bin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

A strategy for introducing an endangered plant Mosla hangchowensis to urban area based on nitrogen preference - Mei-Ying Fan; Kai-Xuan Pan; Wen-Juan Han; Yi-Jun Lu; Qi Shen; Meng Wang; Yuan Ren; Ze-Long Qu; Jie Chang; Ying Ge (Acta Physiologiae Plantarum, 2016)

Modulation of Nav1.8 by Lysophosphatidic Acid in the Induction of Bone Cancer Pain - Hai-Li Pan; Ben-Long Liu; Wei Lin; Yu-Qiu Zhang (Neuroscience Bulletin, 2016)

Effect of the inclined weak interlayers on the rainfall response of a bedded rock slope - Long-qi Li; Neng-pan Ju (Journal of Mountain Science, 2016)

The effect of carbon nanotubes and titanium dioxide incorporated in PDMS on biofilm community composition and subsequent mussel plantigrade settlement - Jin-Long Yang; Yi-Feng Li; Xing-Pan Guo; Xiao Liang; Yue-Feng Xu; De-Wen Ding; Wei-Yang Bao; Sergey Dobretsov (Biofouling, 2016)

Arsenic modulates the composition of anode-respiring bacterial community during dry-wet cycles in paddy soils - Ya-Jie Wang; Zheng Chen; Pan-Pan Liu; Guo-Xin Sun; Long-Jun Ding; Yong-Guan Zhu (Journal of Soils and Sediments, 2016)

Development of Dryland Oilseed Production Systems in Northwestern Region of the USA - D. S. Long; F. L. Young; W. F. Schillinger; C. L. Reardon; J. D. Williams; B. L. Allen; W. L. Pan; D. J. Wysocki (BioEnergy Research, 2016)

Estimating the sensitivity of runoff to climate change in an alpine-valley watershed of Xinjiang, China - Ling Wang; Hai-Long Liu; An-Ming Bao; Xiang-Liang Pan; Xi Chen (Hydrological Sciences Journal, 2016)

Molecular Cloning and Characterization of Two Genes Encoding Tryptophan Decarboxylase from Aegilops variabilis with Resistance to the Cereal Cyst Nematode (Heterodera avenae) and Root-Knot Nematode (Meloidogyne naasi) - Lin Li; Minghui Zheng; Hai Long; Guangbing Deng; Atsushi Ishihara; Feng Liu; Junjun Liang; Zhifen Pan; Maoqun Yu (Plant Molecular Biology Reporter, 2016)

A Single Nucleotide Polymorphism of Nud Converts the Caryopsis Type of Barley (Hordeum Vulgare L.) - Shuiyang Yu; Hai Long; Guangbing Deng; Zhifen Pan; Junjun Liang; Xingquan Zeng; Yawei Tang; Nyima Tashi; Maoqun Yu (Plant Molecular Biology Reporter, 2016)

Physiological characterization of maize tolerance to low dose of aluminum, highlighted by promoted leaf growth - Liang Wang; Xian-Wei Fan; Jian-Long Pan; Zhang-Bao Huang; You-Zhi Li (Planta, 2015)

Transcriptome profiling of trichome-less reveals genes associated with multicellular trichome development in Cucumis sativus - Jun-Long Zhao; Yun-Li Wang; Dan-Qing Yao; Wen-Ying Zhu; Long Chen; Huan-Le He; Jun-Song Pan; Run Cai (Molecular Genetics and Genomics, 2015)

Localization of the powdery mildew resistance gene Pm07J126 in wheat (Triticum aestivum L.) - Shuiyang Yu; Hai Long; Guangbing Deng; Zhifen Pan; Junjun Liang; Maoqun Yu (Euphytica, 2015)

Preparation of TiO2/Silicalite-2@CoFe2O4 Magnetic Composites and Evaluation of their Photocatalytic Activity in Cr(VI) Removal - Mang Lu; Yue Cheng; Shun-long Pan; Ting-ling Yang; Zhong-zhi Zhang (Water, Air, & Soil Pollution, 2015)

Plant regeneration from shoot regrowth and de novo embryo-like structures from cryopreserved shoot tips of Lilium spp. - Wen-Lu Bi; Zhen-Fang Yin; Liang Guo; Long Chen; Chen Pan; Qiao-Chun Wang (In Vitro Cellular & Developmental Biology - Plant, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Diversity and bioprospecting of culturable actinomycetes from marine sediment of the Yellow Sea, China - Zhi-Qiang Xiong; Qiao-Xia Liu; Zhao-Long Pan; Na Zhao; Zhi-Xiang Feng; Yong Wang (Archives of Microbiology, 2015)

A novel species of ellipsoidal multicellular magnetotactic prokaryotes from L ake Y uehu in C hina - Yi‐Ran Chen; Rui Zhang; Hai‐Jian Du; Hong‐Miao Pan; Wen‐Yan Zhang; Ke Zhou; Jin‐Hua Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2015)
Summary Two morphotypes of multicellular magnetotactic prokaryotes ( MMPs ) have been identified: spherical (several species) and ellipsoidal (previously one species). Here, we report novel ellipsoidal MMPs that are ∼ 10 × 8 μm in size, and composed of about 86 cells arranged in six to eight interlaced circles. Each MMP was composed of cells that synthesized either bullet‐shaped magnetite magnetosomes alone, or both bullet‐shaped magnetite and rectangular greigite magnetosomes. They showed north‐seeking magnetotaxis, ping‐pong motility and negative phototaxis at a velocity up to 300 μm s −1 . During reproduction, they divided along either their long‐ or short‐body axes. For genetic analysis, we sorted the ellipsoidal MMPs with micromanipulation and amplified their genomes using multiple displacement amplification. We sequenced the 16 S r RNA gene and found 6.9% sequence divergence from that of ellipsoidal MMPs , Candidatus Magnetananas tsingtaoensis and > 8.3% divergence from those of spherical MMPs . Therefore, the novel MMPs belong to different species and genus compared with the currently known ellipsoidal and spherical MMPs respectively. The novel MMPs display a morphological cell differentiation, implying a potential division of labour. These findings provide new insights into the diversity of MMPs in general, and contribute to our understanding of the evolution of multicellularity among prokaryotes.

Valproic Acid Alleviates Memory Deficits and Attenuates Amyloid-β Deposition in Transgenic Mouse Model of Alzheimer’s Disease - Ai-Guo Xuan; Xue-Bing Pan; Peng Wei; Wei-Dong Ji; Wen-Juan Zhang; Ji-Hong Liu; Le-Peng Hong; Wen-Liang Chen; Da-Hong Long (Molecular Neurobiology, 2015)

Distribution of metals and brominated flame retardants (BFRs) in sediments, soils and plants from an informal e-waste dismantling site, South China - Junxia Wang; Lili Liu; Jinfu Wang; Bishu Pan; Xiaoxu Fu; Gang Zhang; Long Zhang; Kuangfei Lin (Environmental Science and Pollution Research, 2015)

Induction of autophagy in human neuroblastoma SH-SY5Y cells by tri-ortho-cresyl phosphate - Ding-Xin Long; Dan Hu; Pan Wang; Yi-Jun Wu (Molecular and Cellular Biochemistry, 2014)

Birth intervention and non-maternal infant-handling during parturition in a nonhuman primate - Wenshi Pan; Tieliu Gu; Yue Pan; Chunguang Feng; Yu Long; Yi Zhao; Hao Meng; Zuhong Liang; Meng Yao (Primates, 2014)

Collection and evaluation of Primula species of western Sichuan in China - Yin Jia; Jing-Long Zhao; Yuan-Zhi Pan; Ying Xu; Ling-Xia Sun; Qing-Lin Liu (Genetic Resources and Crop Evolution, 2014)

Life with compass: diversity and biogeography of magnetotactic bacteria - Wei Lin; Dennis A. Bazylinski; Tian Xiao; Long‐Fei Wu; Yongxin Pan (Environmental Microbiology, 2014)
Summary Magnetotactic bacteria ( MTB ) are unique in their ability to synthesize intracellular nano‐sized minerals of magnetite and/or greigite magnetosomes for magnetic orientation. Thus, they provide an excellent model system to investigate mechanisms of biomineralization. MTB play important roles in bulk sedimentary magnetism and have numerous versatile applications in paleoenvironmental reconstructions, and biotechnological and biomedical fields. Significant progress has been made in recent years in describing the composition of MTB communities and distribution through innovative cultivation‐dependent and ‐independent techniques. In this review, the most recent contributions to the field of diversity and biogeography of MTB are summarized and reviewed. Emphasis is on the novel insights into various factors/processes potentially affecting MTB community distribution. An understanding of the present‐day biogeography of MTB , and the ruling parameters of their spatial distribution, will eventually help us predict MTB community shifts with environmental changes and assess their roles in global iron cycling.

The high-level accumulation of n-3 polyunsaturated fatty acids in transgenic pigs harboring the n-3 fatty acid desaturase gene from Caenorhabditis briggsae - Yanrong Zhou; Yanli Lin; Xiaojie Wu; Chong Feng; Chuan Long; Fuyin Xiong; Ning Wang; Dengke Pan; Hongxing Chen (Transgenic Research, 2014)

Comparative genomic analysis provides insights into the evolution and niche adaptation of marine M agnetospira sp. QH ‐2 strain - Boyang Ji; Sheng‐Da Zhang; Pascal Arnoux; Zoe Rouy; François Alberto; Nadège Philippe; Dorothée Murat; Wei‐Jia Zhang; Jean‐Baptiste Rioux; Nicolas Ginet; Monique Sabaty; Sophie Mangenot; et al. (Environmental Microbiology, 2014)
Summary Magnetotactic bacteria ( MTB ) are capable of synthesizing intracellular organelles, the magnetosomes, that are membrane‐bounded magnetite or greigite crystals arranged in chains. Although MTB are widely spread in various ecosystems, few axenic cultures are available, and only freshwater M agnetospirillum spp. have been genetically analysed. Here, we present the complete genome sequence of a marine magnetotactic spirillum, M agnetospira sp. QH ‐2. The high number of repeats and transposable elements account for the differences in QH ‐2 genome structure compared with other relatives. Gene cluster synteny and gene correlation analyses indicate that the insertion of the magnetosome island in the QH ‐2 genome occurred after divergence between freshwater and marine magnetospirilla. The presence of a sodium‐quinone reductase, sodium transporters and other functional genes are evidence of the adaptive evolution of M agnetospira sp. QH ‐2 to the marine ecosystem. Genes well conserved among freshwater magnetospirilla for nitrogen fixation and assimilatory nitrate respiration are absent from the QH ‐2 genome. Unlike freshwater M agnetospirillum spp., marine M agnetospira sp. QH ‐2 neither has TonB and TonB ‐dependent receptors nor does it grow on trace amounts of iron. Taken together, our results show a distinct, adaptive evolution of M agnetospira sp. QH ‐2 to marine sediments in comparison with its closely related freshwater counterparts.

Functional Investigation of Transmembrane Helix 3 in H+-Translocating Pyrophosphatase - Ching-Hung Lee; Yen-Wei Chen; Yun-Tzu Huang; Yih-Jiuan Pan; Chien-Hsien Lee; Shih-Ming Lin; Lin-Kun Huang; Yueh-Yu Lo; Yu-Fen Huang; Yu-Di Hsu; Shih-Chung Yen; Jenn-Kang Hwang; et al. (The Journal of Membrane Biology, 2013)

A study of a rare chromosomal disorder: mosaic 46,XX,del(18)(p11.2)/46,XX,i(18q) - DAN PENG; PAN-PAN LONG; BO WEN; RONG-HUI YU (Journal of Genetics, 2013)

Isolation and characterization of microsatellite loci in the short-tailed pit viper Gloydius brevicaudus (Viperidae) - Li Ma; Qing-Lin Tong; Ce Chen; Ying-Dan Pan; Long-Hui Lin (Conservation Genetics Resources, 2013)

Transjugular intrahepatic portosystemic shunt induced short- and long-term cerebral blood flow variations in cirrhotic patients: an arterial spin labeling MRI study - Gang Zheng; Long Jiang Zhang; Yue Cao; Zhiying Pan; Rong Feng Qi; Ling Ni; Donghong Shi; Xinxin Fan; Guang Ming Lu (Metabolic Brain Disease, 2013)

The Expression Changes of Cystathionine-β-synthase in Brain Cortex After Traumatic Brain Injury - Mingyang Zhang; Haiyan Shan; Yaoqi Wang; Tao Wang; Weili Liu; Long Wang; Lu Zhang; Pan Chang; Wenwen Dong; Xiping Chen; Luyang Tao (Journal of Molecular Neuroscience, 2013)

Effect of Land-Use Change and Artificial Recharge on the Groundwater in an Arid Inland River Basin - Hai-Long Liu; An-Ming Bao; Xiang-Liang Pan; Xi Chen (Water Resources Management, 2013)

Erratum to: Characterization of a genome-specific Gypsy-like retrotransposon sequence and development of a molecular marker specific for Dasypyrum villosum (L.) - Jie Zhang; Hai Long; Zhifen Pan; Junjun Liang; Shuiyang Yu; Guangbing Deng; Maoqun Yu (Journal of Genetics, 2013)

Adaptation of spherical multicellular magnetotactic prokaryotes to the geochemically variable habitat of an intertidal zone - Ke Zhou; Wen‐Yan Zhang; Hong‐Miao Pan; Jin‐Hua Li; Hai‐Dong Yue; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2013)
Summary A combination of microscopic, molecular and biogeochemical methods was used to study the structure, phylogenetics and vertical distribution of spherical multicellular magnetotactic prokaryotes ( MMPs ) of intertidal sediments in the Y ellow S ea. These MMPs were 5.5 μm in diameter and composed of approximately 15–30 cells. They synthesized bullet‐shaped magnetites in chains or clusters. Phylogenetic analysis of 16 S rRNA gene sequences suggested that these MMPs represent a novel species affiliated to the D eltaproteobacteria. To study their vertical distribution and the relationship to geochemical parameters, sediment cores were collected after the redox potential was measured in situ . The sediments were composed of yellow, grey and black layers from the surface to depth. The spherical MMPs were concentrated near the grey‐black layer transition at a depth of 8–12 cm, while coccoid‐shaped magnetotactic bacteria near the yellow‐grey layer transition at a depth of 3–5 cm. The intertidal MMPs showed a deeper distribution at more reduced environments than coccoid‐shaped magnetotactic bacteria, and MMPs in lagoon sediments. Additionally the MMPs were concentrated significantly in layers with high proportion of fine sand and total organic carbon, rich in leachable iron but poor in nitrate. These results show an adaptation of spherical MMPs to the peculiar intertidal sediment habitat.

WHAMM is required for meiotic spindle migration and asymmetric cytokinesis in mouse oocytes - Xin Huang; Lu Ding; Rui Pan; Peng-Fei Ma; Pan-Pan Cheng; Chun-Hui Zhang; Yu-Ting Shen; Lin Xu; Yu Liu; Xiao-Qin He; Zhong-Quan Qi; Hai-Long Wang (Histochemistry and Cell Biology, 2013)

Characterization of a genome-specific Gypsy-like retrotransposon sequence and development of a molecular marker specific for Dasypyrum villosum (L.) - JIE ZHANG; HAI LONG; ZHIFEN PAN; JUNJUN LIANG; SHUIYANG YU; GUANGBING DENG; MAOQUN YU (Journal of Genetics, 2013)

Common Variants in HLA-DRA Gene are Associated with Alcohol Dependence in Two Caucasian Samples - Yue Pan; Ke-Sheng Wang; Liang Wang; Long-Yang Wu (Journal of Molecular Neuroscience, 2013)

Association of CASP9, CASP10 gene polymorphisms and tea drinking with colorectal cancer risk in the Han Chinese population - He Liu; Xia Jiang; Ming-wu Zhang; Yi-feng Pan; Yun-xian Yu; Shan-chun Zhang; Xin-yuan Ma; Qi-long Li; Kun Chen (Journal of Zhejiang University-SCIENCE B, 2013)

Host preference and nymph performance of B and Q putative species of Bemisia tabaci on three host plants - Xiaoguo Jiao; Wen Xie; Shaoli Wang; Qingjun Wu; Long Zhou; Huipeng Pan; Baiming Liu; Youjun Zhang (Journal of Pest Science, 2012)

Mechano growth factor (MGF) promotes proliferation and inhibits differentiation of porcine satellite cells (PSCs) by down-regulation of key myogenic transcriptional factors - Li-Li Qin; Xiao-Kui Li; Jian Xu; De-Lin Mo; Xiong Tong; Zhi-Cheng Pan; Jia-Qi Li; Yao-Sheng Chen; Zhe Zhang; Chong Wang; Qiao-Ming Long (Molecular and Cellular Biochemistry, 2012)

Molecular Cloning, Characterization, and Expression Analysis of Genes Encoding Gibberellin 20-Oxidase in Dasypyrum villosum Dwarf Mutant - P. Cai; H. Long; G. B. Deng; Z. F. Pan; Z. S. Peng; M. Q. Yu (Plant Molecular Biology Reporter, 2012)

Determination of the geographical origin of Chinese teas based on stable carbon and nitrogen isotope ratios - Long Zhang; Jia-rong Pan; Cheng Zhu (Journal of Zhejiang University-SCIENCE B, 2012)

Determination of methylmercury in marine fish from coastal areas of Zhejiang, China - Zhu Huang; Xiao-Dong Pan; Jian-Long Han; Ping-Gu Wu; Jun Tang; Ying Tan (Food Additives & Contaminants Part B-Surveillance, 2012)

Molecular detection of rye (Secale cereale L.) chromatin in wheat line 07jian126 (Triticum aestivum L.) and its association to wheat powdery mildew resistance - Shuiyang Yu; Hai Long; Hong Yang; Jie Zhang; Guangbing Deng; Zhifen Pan; Erliang Zhang; Maoqun Yu (Euphytica, 2012)

Evaluation of M307 of FUT1 gene as a genetic marker for disease resistance breeding of sutai pigs - Wen-bin Bao; Lan Ye; Jing Zhu; Zhang-yuan Pan; Guo-qiang Zhu; Xue-gen Huang; Sheng-long Wu (Molecular Biology Reports, 2012)

The effect of mutation at M307 in FUT1 gene on susceptibility of Escherichia coli F18 and gene expression in Sutai piglets - Wen-bin Bao; Lan Ye; Zhang-yuan Pan; Jing Zhu; Zi-Dong Du; Guo-qiang Zhu; Xue-gen Huang; Sheng-long Wu (Molecular Biology Reports, 2012)

Construction of a high density integrated genetic map for cucumber (Cucumis sativus L.) - Wei-Wei Zhang; Jun-Song Pan; Huan-Le He; Chi Zhang; Zheng Li; Jun-Long Zhao; Xiao-Jun Yuan; Li-Huang Zhu; San-Wen Huang; Run Cai (Theoretical and Applied Genetics, 2012)

Erratum to: The effect of mutation at M307 in FUT1 gene on susceptibility of Escherichia coli F18 and gene expression in Sutai piglets - Wen-bin Bao; Lan Ye; Zhang-yuan Pan; Jing Zhu; Zi-Dong Du; Guo-qiang Zhu; Xue-gen Huang; Sheng-long Wu (Molecular Biology Reports, 2012)

A novel genus of multicellular magnetotactic prokaryotes from the Yellow Sea - Ke Zhou; Wen‐Yan Zhang; Kui Yu‐Zhang; Hong‐Miao Pan; Sheng‐Da Zhang; Wei‐Jia Zhang; Hai‐Dong Yue; Ying Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2012)
Summary Multicellular magnetotactic prokaryotes (MMPs) are a group of magnetotactic microorganisms composed of 10–40 Gram‐negative cells. Currently, all the identified MMPs show a spherical morphology and synthesize mainly iron sulfide magnetosomes. In this study, we report a novel genus of MMPs with peculiar ellipsoidal morphology and iron oxide magnetosomes, which were discovered in intertidal sediment of the Yellow Sea in China. Optical and fluorescence microscopy revealed that this organism was ∼10 × 8 µm in size and composed of ∼40 cells enveloped by an outer layer. Scanning electron microscopy showed that the cells were arranged in 4–6 interlaced circles. Bullet‐shaped magnetite magnetosomes were organized in chains roughly parallel to the long axis of the ellipsoidal MMPs when analysed by transmission electron microscopy. These MMPs displayed special escape motility, i.e. swimming rapidly from the edge to the centre of the droplet and then slowly back to the edge. In addition, they exhibited negative phototaxis. Light microscopy observations showed that the ellipsoidal MMPs reproduced by division along the body long axis. Both analysis of 16S rRNA gene sequence and fluorescence in situ hybridization revealed the ellipsoidal MMPs as a new genus of the Deltaproteobacteria . In summary, this novel genus of MMPs exhibit unique morphology, peculiar division process and distinct phylogenetic affiliation compared with the other MMPs.

Sequence polymorphism and expression analysis of genes encoding gibberellin 20-oxidase from Dasypyrus villosum - P. Cai; H. Long; J. Liang; C. Wang; G. Deng; Z. Pan; Z. Peng; M. Yu (Cereal Research Communications, 2011)

Beneficial genotype of swine FUT1 gene governing resistance to E. coli F18 is associated with important economic traits - WEN-BIN BAO; LAN YE; ZHANG-YUAN Pan; JIN ZHU; GUO-QIANG ZHU; XUE-GEN HUANG; SHENG-LONG WU (Journal of Genetics, 2011)

Fluid Dynamics Analysis of a Novel Micropatterned Cell Bioreactor - Yuhong Cui; Bo Huo; Shujin Sun; Fan Yang; Yuxin Gao; Jun Pan; Mian Long (Annals of Biomedical Engineering, 2011)

Selective Pressure to Increase Charge in Immunodominant Epitopes of the H3 Hemagglutinin Influenza Protein - Keyao Pan; Jinxue Long; Haoxin Sun; Gregory J. Tobin; Peter L. Nara; Michael W. Deem (Journal of Molecular Evolution, 2011)

Ovate family protein 1 as a plant Ku70 interacting protein involving in DNA double-strand break repair - Yung-Kai Wang; Wen-Chi Chang; Pei-Feng Liu; Mu-Kai Hsiao; Chueh-Tsun Lin; Shih-Ming Lin; Rong-Long Pan (Plant Molecular Biology, 2010)

Development of a large-scale isolation chamber system for the safe and humane care of medium-sized laboratory animals harboring infectious diseases - Xin Pan; Jian-cheng Qi; Ming Long; Hao Liang; Xiao Chen; Han Li; Guang-bo Li; Hao Zheng (Journal of Zhejiang University-SCIENCE B, 2010)

Efficient production of omega-3 fatty acid desaturase (sFat-1)-transgenic pigs by somatic cell nuclear transfer - DengKe Pan; Li Zhang; YanRong Zhou; Chong Feng; Chuan Long; Xiao Liu; Rong Wan; Jian Zhang; AiXing Lin; EnQiu Dong; ShuChen Wang; HouGang Xu; et al. (Science China Life Sciences, 2010)

BMP-2/PLGA Delayed-Release Microspheres Composite Graft, Selection of Bone Particulate Diameters, and Prevention of Aseptic Inflammation for Bone Tissue Engineering - Ye Ji; Gong ping Xu; Zhi peng Zhang; Jing jun Xia; Jing long Yan; Shang ha Pan (Annals of Biomedical Engineering, 2010)

TM4SF3 promotes esophageal carcinoma metastasis via upregulating ADAM12m expression - Zhuan Zhou; Yu-Liang Ran; Hai Hu; Jian Pan; Zhi-Feng Li; Li-Zhao Chen; Li-Chao Sun; Liang Peng; Xi-Lu Zhao; Long Yu; Li-Xin Sun; Zhi-Hua Yang (Clinical & Experimental Metastasis, 2008)

Characterization of a homogeneous taxonomic group of marine magnetotactic cocci within a low tide zone in the China Sea - Hongmiao Pan; Kailing Zhu; Tao Song; Kui Yu‐Zhang; Christopher Lefèvre; Sue Xing; Min Liu; Sanjun Zhao; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2008)
Summary Magnetotactic bacteria are a heterologous group of motile prokaryotes, ubiquitous in aquatic habitats and cosmopolitan in distribution. Here, we studied the diversity of magnetotactic bacteria in a seawater pond within an intertidal zone at Huiquan Bay in the China Sea. The pond is composed of a permanently submerged part and a low tide subregion. The magnetotactic bacteria collected from the permanently submerged part display diversity in morphology and taxonomy. In contrast, we found a virtually homogenous population of ovoid‐coccoid magnetotactic bacteria in the low tide subregion of the pond. They were bilophotrichously flagellated and exhibited polar magnetotactic behaviour. Almost all cells contained two chains of magnetosomes composed of magnetite crystals. Intriguingly, the combination of restriction fragment length polymorphism analysis (RFLP) and sequencing of cloned 16S rDNA genes from the low tide subregion samples as well as fluorescence in situ hybridization (FISH) revealed the presence of a homogenous population. Moreover, phylogenetic analysis indicated that the Qingdao Huiquan low tide magnetotactic bacteria belong to a new genus affiliated with the α‐subclass of Proteobacteria . This finding suggests the adaptation of the magnetotactic bacterial population to the marine tide.

Cloning and Characterization of a Novel, Human Cellular Retinaldehyde-binding Protein CRALBP-like (CRALBPL) Gene - Ya-Hui Kong; Guang-Ming Ye; Kai Qu; Wen-Qi Pan; Xiang-Hua Liu; Bo Wan; Jin-Hu Guo; Long Yu (Biotechnology Letters, 2006)

New Fluorescent Labels: 4- and 7-Chlorofluorescein - Feng-Yan Ge; Xi-Long Yan; Fan-Yong Yan; Hui-Ying Pan; Li-Gong Chen (Journal of Fluorescence, 2005)

Small heat-shock protein 22 mutated in autosomal dominant Charcot-Marie-Tooth disease type 2L - Bei-sha Tang; Guo-hua Zhao; Wei Luo; Kun Xia; Fang Cai; Qian Pan; Ru-xu Zhang; Fu-feng Zhang; Xiao-min Liu; Biao Chen; Cheng Zhang; Lu Shen; et al. (Human Genetics, 2005)

Effective induction of therapeutic antitumor immunity by dendritic cells coexpressing interleukin-18 and tumor antigen - Dajing Xia; Shu Zheng; Weiping Zhang; Long He; Qingqing Wang; Jianping Pan; Lihuang Zhang; Jianli Wang; Xuetao Cao (Journal of Molecular Medicine, 2003)

Mutation analysis of hereditary multiple exostoses in the Chinese - L. Xu; J. Xia; H. Jiang; J. Zhou; H. Li; D. Wang; Q. Pan; Z. Long; C. Fan; H.-X. Deng (Human Genetics, 1999)